Positive electrode active material, method for producing positive electrode active material, and rechargeable lithium battery
Patent Information
- Application Number
- CN202610555255.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2026-04-15
- Filing Date
- 2026-04-24
- Publication Date
- 2026-10-27
AI Technical Summary
但是这样的粘结剂相对昂贵,这具有增加电池的制造成本的缺点
[0011]根据一些实施方式的制造正电极活性物质的方法可在使制造成本最小化的同时提供实现优异的容量特性和电极板的粘合强度的正电极活性物质。
Smart Images

Figure CN122992018A_ABST
Abstract
Description
Technical Field
[0001] The invention discloses a positive electrode active material, a method for preparing the positive electrode active material, and a rechargeable lithium battery. Background Technology
[0002] Portable information devices such as cellular phones, laptops, and smartphones use rechargeable lithium batteries. Electric vehicles also use rechargeable lithium batteries with high energy density as their power source.
[0003] Further research has been conducted to use rechargeable lithium-ion batteries with high energy density as a driving power source or energy storage source for hybrid or electric vehicles. For example, attempts have been made to increase the amount of active material in the positive electrode to improve the energy density of rechargeable lithium-ion batteries.
[0004] By adding a binder during the manufacturing process of the positive electrode plate, the adhesive strength of the positive electrode plate (i.e., the adhesive strength between the positive electrode current collector and the positive electrode active material) is improved. Adhesion prevents the active material from detaching from the current collector and improves the conductivity (electrical conductivity) of the positive electrode. However, when the amount of binder increases to provide sufficient adhesive force between the current collector and the active material, the amount of active material decreases, leading to a reduction in battery capacity and energy density.
[0005] In addition, polymers such as polyvinyl alcohol, polyvinyl chloride, and polyvinyl fluoride are commonly used as binders. However, such binders are relatively expensive, which increases the manufacturing cost of the battery. Summary of the Invention
[0006] Embodiments of this disclosure provide a positive electrode active material that can improve the adhesion strength and conductivity of electrode plates while ensuring cost-effectiveness and high capacity, a method for manufacturing the positive electrode active material, and a rechargeable lithium battery.
[0007] In some instances, the positive electrode active material includes: a core particle comprising a lithium transition metal complex compound; and a coating layer disposed on the surface of the core particle, wherein the coating layer comprises graphene having a layered structure of 2 to 50 layers.
[0008] In some instances, methods for preparing positive electrode active materials include: preparing (preparing) core particles comprising a lithium transition metal complex; preparing graphite microparticles having an average size of less than or equal to about 2.5 μm; and mixing the core particles and graphite microparticles to obtain the positive electrode active material.
[0009] In some instances, a rechargeable lithium battery includes: a positive electrode comprising a current collector and a layer of positive electrode active material on the current collector, wherein the layer of positive electrode active material comprises the positive electrode active material; a negative electrode; and an electrolyte.
[0010] The positive electrode active material according to some embodiments is very economical and has high capacity characteristics. Furthermore, using the aforementioned positive electrode active material, the adhesion strength and conductivity of the electrode plate can be maximized. Additionally, a positive electrode including the aforementioned positive electrode active material and a rechargeable lithium battery can have improved energy density.
[0011] The method for manufacturing positive electrode active material according to some embodiments can provide positive electrode active material that achieves excellent capacity characteristics and adhesion strength of electrode plates while minimizing manufacturing costs. Attached Figure Description
[0012] Figure 1 A schematic perspective view of a cylindrical rechargeable lithium battery.
[0013] Figure 2 This is a cross-sectional view of a prismatic rechargeable lithium battery.
[0014] Figure 3 and 4 A schematic exploded perspective view of a pouch-type rechargeable lithium battery.
[0015] Figure 5 This is a scanning electron microscope image of the surface of the flake graphite used in the preparation of the positive electrode active material in Example 1.
[0016] Figure 6 These are scanning electron microscope images of the surface of graphite particles obtained by crushing flake graphite.
[0017] Figure 7 This is a scanning electron microscope image of the surface of the carbon nanotube raw material used in the preparation of the positive electrode active material in Example 4.
[0018] Figure 8 These are scanning electron microscope images of the surface of carbon nanotubes obtained by crushing carbon nanotube raw materials.
[0019] Figure 9 This is a scanning electron microscope image of the surface of the coated raw material used in the preparation of the positive electrode active material in Example 5, in which graphite microparticles and carbon nanotubes are combined.
[0020] Figure 10 This is a scanning electron microscope image of the surface of the positive electrode active material prepared in Example 1.
[0021] Figure 11 This is a scanning electron microscope image of the surface of the positive electrode active material prepared in Comparative Example 1.
[0022] Figure 12This is a scanning electron microscope image of the surface of the positive electrode active material prepared in Comparative Example 3.
[0023] Figure 13 This is a scanning electron microscope image of the surface of the positive electrode active material prepared in Comparative Example 4.
[0024] Figure 14 This is a scanning electron microscope image of the surface of the positive electrode active material prepared in Comparative Example 5.
[0025] Figure 15 This is a transmission electron microscope image of the cross-section of the coating layer of the positive electrode active material prepared in Example 1.
[0026] Figure 16 This is a transmission electron microscope image of the cross-section of the coating layer of the positive electrode active material prepared in Comparative Example 1.
[0027] Figure 17 This is a scanning electron microscope image of the surface of the positive electrode active material prepared in Example 4.
[0028] Figure 18 This is a scanning electron microscope image of the surface of the positive electrode active material prepared in Example 5.
[0029] Figure 19 This is a scanning electron microscope image of the surface of the positive electrode active material prepared in Comparative Example 6. Detailed Implementation
[0030] Specific embodiments will be described in detail below so that those skilled in the art can readily implement them. However, this disclosure may be embodied in many different forms and is not limited to the embodiments set forth herein.
[0031] The terminology used herein is for descriptive purposes only and is not intended to limit the scope of this disclosure. Unless the context clearly specifies otherwise, singular expressions include plural expressions.
[0032] "Combination" refers to mixtures, laminates, complexes, copolymers, alloys, blends, reaction products, etc., of the constituent elements.
[0033] In this document, it should be understood that terms such as “comprising,” “including,” or “having” are intended to specify the presence of the features, quantities, steps, elements, or combinations thereof embodied, but do not preclude the possibility of the presence or addition of one or more other features, quantities, steps, elements, or combinations thereof.
[0034] In the accompanying drawings, for clarity, the thickness of layers, films, panels, regions, etc., may be exaggerated, and the same reference numerals denote the same elements throughout the specification. It will be understood that when an element, such as a layer, film, region, or substrate, is referred to as being "on" another element, it may be directly on said other element, or there may be intermediate elements present. In contrast, when an element is referred to as being "directly on" another element, there are no intermediate elements.
[0035] The term "layer" in this article includes not only the shape that forms on the entire surface when viewed from a plan view, but also the shape that forms on a portion of the surface.
[0036] The average particle size can be measured by methods well known to those skilled in the art, such as by a particle size analyzer or by transmission electron microscopy or scanning electron microscopy images. Alternatively, the average particle size value can be obtained by measuring using dynamic light scattering, performing data analysis, counting the number of particles for each particle size range, and calculating from there. Unless otherwise defined, the average particle size may mean the diameter D of particles having a cumulative volume of 50% of the particle size distribution. 50 As used herein, unless otherwise defined, mean particle size means the diameter D of the particles having a cumulative volume of 50% of the particle size in a particle size distribution obtained by randomly measuring the size (diameter or major axis length) of approximately 20 particles in a scanning electron microscope image. 50 .
[0037] In this article, "or" will not be interpreted as having an exclusive meaning. For example, "A or B" will be interpreted as including A, B, A+B, etc.
[0038] "Metals" include common metals, transition metals, and metalloids (semi-metals).
[0039] Positive electrode active material
[0040] According to some embodiments, the positive electrode active material includes: a core particle comprising a lithium transition metal complex compound; and a coating layer disposed on the surface of the core particle, wherein the coating layer comprises graphene having a layered structure of about 2 to about 50 layers.
[0041] Typically, positive electrodes are manufactured by adding binders and conductive materials to improve the adhesion strength between the positive electrode current collector and the positive electrode active material, and to improve the conductivity of the positive electrode. However, there is a problem that as the amount of binder and conductive material increases, the amount of positive electrode active material decreases, which reduces the energy density of the battery. However, the positive electrode active material according to embodiments of this disclosure includes a coating layer containing graphene with a layered structure having about 2 to about 50 layers, wherein even if a small amount of carbon material is coated on the surface of the active material particles, adhesion strength and conductivity can be increased. Therefore, even if a small amount of binder and conductive material is used in the manufacture of the positive electrode, high adhesion strength and conductivity with the electrode plate can be provided. In addition, since the amount of binder and conductive material used in the manufacture of the positive electrode is reduced, the amount of positive electrode active material can be increased by the same amount, thereby providing high capacity and high energy density in rechargeable lithium batteries including positive electrode active material.
[0042] On the other hand, if a coating layer is provided using a crystalline carbon material with low dispersibility, a problem arises: the carbon material can aggregate, making it difficult to uniformly provide the coating layer on the surface of the core particle. However, by appropriately selecting the crystalline carbon material from which the coating layer originates and by applying the coating under suitable conditions, the positive electrode active material according to some embodiments can have a coating layer with a thin and uniform thickness. The coating layer has a layered structure, exhibiting a dense crystalline structure, and includes crystalline carbon provided in a two-dimensional plane on the surface of the core particle. Therefore, the resistivity of the positive electrode active material is reduced and the electronic conductivity is improved. Consequently, lithium ions can be more effectively inserted and extracted and diffuse along the layered structure, thereby improving ionic conductivity. Even if the positive electrode including such a positive electrode active material comprises very little or no individual conductive material, the positive electrode can still have excellent electronic conductivity and low resistance. And even if the positive electrode includes a very small amount of binder, the positive electrode can still have high electrode plate adhesion strength. Rechargeable lithium batteries with such positive electrodes can have high capacity and energy density, as well as improved overall electrochemical performance such as charging and discharging efficiency and rate performance.
[0043] Methods have been proposed for using graphene as a raw material to form a graphene-containing coating layer on the surface of the core particles of a positive electrode active material. However, such methods are limited in commercialization due to their complex and expensive coating process, and it is difficult to provide a film-type coating layer with uniform thickness on the surface of the core particles using such methods. Additionally, techniques for coating amorphous carbon on the surface of core particles have been proposed, but it is difficult to provide uniform coating and increased energy density using such methods, and it is also difficult to increase the electronic conductivity and reduce the resistance of the positive electrode. According to some embodiments, the positive electrode active material introduces a uniform film-type graphene layer with a thickness of about 2 to about 50 atomic layers, or a few nanometers to tens of nanometers, onto the surface of the core particles. Compared to coating amorphous carbon or conventional crystalline carbon, the positive electrode active material of this disclosure can exhibit very high electronic and ionic conductivity, increased energy density, reduced resistance, and excellent electrochemical performance. In addition, the positive electrode active material of the embodiment uses graphite (a low-cost material) and is provided by a dry coating method that is advantageous for cost reduction, good processability and large-scale production.
[0044] The preparation of positive electrode active materials according to some embodiments of this disclosure is described in detail below.
[0045] Core Particles
[0046] The core particles comprise lithium transition metal complex compounds. These lithium transition metal complex compounds may include, for example, lithium nickel-based oxides, lithium cobalt-based oxides, lithium manganese-based oxides, lithium iron phosphate (LiFePO4)-based compounds, cobalt-free lithium nickel manganese-based oxides, lithium manganese-rich complex oxides, or combinations thereof.
[0047] In some instances, the lithium transition metal complex of the core particle can be a compound represented by any of the following chemical formulas: Li a A 1-b X b O 2-c D c (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05); Li a Mn 2-b X b O 4-c D c (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05); Li a Ni 1-b-c Co b X c O 2-α D α(0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.5, 0<α<2); Li a Ni 1-b-c Mn b X c O 2-α D α (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.5, 0<α<2); Li a Ni b Co c L 1 d G e O2 (0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5, 0≤e≤0.1); Li a NiG b O2 (0.90≤a≤1.8, 0.001≤b≤0.1); Li a CoG b O2 (0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn 1-b G b O2 (0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn2G b O4 (0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn 1-g G g PO4 (0.90≤a≤1.8, 0≤g≤0.5); Li (3-f) Fe2(PO4)3 (0≤f≤2); Li a FePO4 (0.90≤a≤1.8). In these chemical formulas, A is at least one of Ni, Co, and Mn; X is at least one of Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, and rare earth elements; D is at least one of F, S, and P; G is at least one of Al, Cr, Mn, Fe, Mg, La, Ce, Sr, and V; and L 1 It is at least one of Mn and Al.
[0048] In a further example, the lithium transition metal complex of the core particle may be a lithium cobalt-based oxide represented by Formula 1, a lithium nickel-based oxide represented by Formula 2, a lithium iron phosphate-based compound represented by Formula 3, a cobalt-free lithium nickel manganese-based oxide represented by Formula 4, or a combination thereof.
[0049] [Chemical Formula 1]
[0050] Lia1 Co x1 M 1 y1 O 2-b1 X b1
[0051] In chemical formula 1, 0.9 ≤ a1 ≤ 1.8, 0.7 ≤ x1 ≤ 1, 0 ≤ y1 ≤ 0.3, 0.9 ≤ x1 + y1 ≤ 1.1, and 0 ≤ b1 ≤ 0.1, M 1 X is at least one of Al, B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mn, Mo, Ni, Se, Si, Sn, Sr, Ti, V, W, Y, Zn, and Zr, and X is at least one of F, P, and S.
[0052] [Chemical Formula 2]
[0053] Li a2 Ni x2 M 2 y2 M 3 z2 O 2-b2 X b2
[0054] In chemical formula 2, 0.9 ≤ a² ≤ 1.8, 0.3 ≤ x² ≤ 1, 0 ≤ y² ≤ 0.7, 0 ≤ z² ≤ 0.7, 0.9 ≤ x² + y² + z² ≤ 1.1, and 0 ≤ b² ≤ 0.1, M 2 and M 3 Each of the following is independently at least one of Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ti, V, Y, W, and Zr, and X is at least one of F, P, and S. In a further embodiment of chemical formula 2, 0.6≤x²≤1, 0≤y²≤0.4, and 0≤z²≤0.4; 0.8≤x²≤1, 0≤y²≤0.2, and 0≤z²≤0.2; 0.4≤x²≤1, 0≤y²≤0.6, and 0≤z²≤0.6; 0.5≤x²≤1, 0≤y²≤0.5, and 0≤z²≤0.5; 0.4≤x²≤0.8, 0≤y²≤0.2, and 0≤z²≤0.4; or 0.4≤x²≤0.6, 0≤y²≤0.2, and 0≤z²≤0.3.
[0055] [Chemical Formula 3]
[0056] Li a3 Fe x3 M 4 y3 PO 4-b3 X b3
[0057] In Chemical Formula 3, 0.9≤a3≤1.8, 0.6≤x3≤1, 0≤y3≤0.4, and 0≤b3≤0.1, M 4 is one or more of Al, B, Ba, Ca, Ce, Co, Cr, Cu, Mg, Mn, Mo, Ni, Se, Si, Sn, Sr, Ti, V, W, Y, Zn, and Zr, and X is at least one of F, P, and S.
[0058] [Chemical Formula 4]
[0059] Li a4 Ni x4 Mn y4 M 5 z4 O 2-b4 X b4
[0060] In Chemical Formula 4, 0.9≤a4≤1.8, 0.8≤x4<1, 0<y4≤0.2, 0≤z4≤0.2, 0.9≤x4+y4+z4≤1.1, and 0≤b4≤0.1, M 5 is at least one of Al, B, Ba, Ca, Ce, Cr, Fe, Mg, Mo, Nb, Si, Sn, Sr, Ti, V, W, Y, and Zr, and X is at least one of F, P, and S.
[0061] In some examples, the lithium transition metal composite compound of the core particles may include a lithium cobalt-based oxide represented by Chemical Formula 1. In such cases, high-voltage design of the rechargeable lithium battery and reduced gas generation under high voltage may be possible. Accordingly, the reliability and safety of the rechargeable lithium battery may be improved, and battery resistance may be suppressed by achieving a synergistic effect in a fast charging system.
[0062] In further examples, the lithium transition metal composite compound of the core particles may include a lithium nickel-based oxide represented by Chemical Formula 2. In such cases, a rechargeable lithium battery with high capacity and high energy density may be realized.
[0063] When the lithium transition metal complex of the core particles is a lithium nickel-based oxide, the positive electrode active material can be a medium nickel-based positive electrode active material. Here, based on 100 mol% of the total metal excluding lithium in the lithium nickel-based oxide of the core particles, nickel can be included in amounts of about 40 mol% to about 80 mol%, for example, about 45 mol% to about 75 mol%, about 50 mol% to about 70 mol%, about 50 mol% to about 65 mol%, or about 55 mol% to about 65 mol%. When the amount of nickel is within these ranges, the rechargeable lithium battery can be operated at high voltages while having reduced side reactions with the electrolyte, thereby preventing electrochemical or chemical mechanical degradation at high voltages and thus providing long cycle life characteristics.
[0064] When the positive electrode active material is a medium-nickel-based positive electrode active material, cobalt may be included in an amount from about 5 mol% to about 30 mol%, for example, from about 7 mol% to about 28 mol%, from about 8 mol% to about 25 mol%, or from about 10 mol% to about 20 mol% of the total metal excluding lithium in 100 mol% of the in-core nickel-based oxide, for example, from about 5 mol% to about 30 mol%, from about 7 mol% to about 28 mol%, from about 8 mol% to about 25 mol%, or from about 10 mol% to about 20 mol%. When the amount of cobalt is within these ranges, the rechargeable lithium battery can operate at high voltages without electrochemical or chemomechanical degradation at high voltages, and therefore can have long cycle life characteristics.
[0065] When the positive electrode active material is a medium-nickel-based positive electrode active material, manganese may be included in an amount from about 10 mol% to about 50 mol%, for example, from about 15 mol% to about 45 mol%, from about 20 mol% to about 40 mol%, or from about 25 mol% to about 35 mol% of the total metal excluding lithium in 100 mol% of the in-core nickel-based oxide, for example, from about 10 mol% to about 50 mol%, from about 15 mol% to about 45 mol%, from about 20 mol% to about 40 mol%, or from about 25 mol% to about 35 mol%. When the amount of manganese is within these ranges, the rechargeable lithium battery can operate at high voltages without electrochemical or chemomechanical degradation at high voltages, and therefore can have long cycle life characteristics.
[0066] When the lithium transition metal complex of the core particle is a lithium nickel-based oxide, the positive electrode active material can be a high-nickel-based positive electrode active material. For example, based on 100 mol% of the total metals excluding lithium in the lithium nickel-based oxide of the core particle, the amount including nickel can be greater than or equal to about 80 mol%, for example, greater than or equal to about 85 mol%, greater than or equal to about 90 mol%, greater than or equal to about 91 mol%, or greater than or equal to about 94 mol% and less than or equal to about 99 mol%. In such cases, the core particle can be a high-nickel positive electrode active material. Because high-nickel positive electrode active materials can have high capacity, they can provide high capacity and high density in rechargeable lithium batteries.
[0067] When the lithium transition metal composite compound of the core particle is a lithium nickel-based oxide, the core particle can be in the form of a secondary particle. Because the secondary particle is formed by tightly agglomerating the primary particle, the secondary particle can be spherical, ellipsoidal, polyhedral, or irregular in shape, and the primary particles constituting the secondary particle can be spherical, ellipsoidal, plate-shaped, or a combination thereof.
[0068] When the lithium transition metal composite compound of the core particle is a lithium nickel-based oxide and the core particle is in the form of secondary particles, the average particle size D of the secondary particles in the core particle is... 50 The size can be from about 6 μm to about 25 μm, for example, from about 6 μm to about 23 μm, from about 7 μm to about 20 μm, or from about 8 μm to about 15 μm. The average size of the primary particles constituting the secondary particles can be from about 10 nm to about 1 μm, for example, from about 10 nm to about 800 nm, from about 20 nm to about 500 nm, or from about 50 nm to about 200 nm. Here, the average particle size D of the secondary particles is... 50 The particle size distribution can be obtained by randomly selecting approximately 20 particles from the scanning electron microscope (SEM) images of the secondary particles, measuring their particle size (diameter, major axis, or major axis length), and then taking the size of the particles with a cumulative volume of 50% as the average particle size. Additionally, the size of the primary particles constituting the secondary particles can be measured using electron backscatter diffraction (EBSD) analysis. EBSD measurement equipment can be, for example, a Bruker QUANTAX EBSD, and the sample can be ion-milled (ground) using a CP (Cross-sectional Polisher, Ilion+, Gatan). EBSD can be measured using a Bruker e-flash HR EBSD detector at an accelerating voltage of 20 keV. In EBSD analysis, each grain (i.e., primary particle) in the cross-sectional electron microscope image of the secondary particles can be represented by a different color, and the cross-sectional area of a grain can be measured to obtain a circle with the same area, and the diameter of this circle can be calculated as the size of the corresponding grain. In this way, the size of the grains captured in the image can be measured, and their arithmetic mean can be calculated as the average size of the grains measured by EBSD.
[0069] The average particle size D of the core particles 50 The diameter can be approximately 1 μm to approximately 25 μm, approximately 3 μm to approximately 22 μm, or approximately 10 μm to approximately 18 μm. When the average particle size D of the core particles... 50Within these ranges, the adhesion strength of the positive electrode active material to the current collector (i.e., the adhesion strength of the electrode plate) is improved, thereby enhancing the structural stability of the positive electrode active material. Furthermore, the stability of the positive electrode slurry and the mixing density (mixture density) of the electrode plate can be improved during the positive electrode manufacturing process. Moreover, because lithium ions travel a longer path before reaching the surface of the positive electrode active material, the formation of impurities on the surface of the positive electrode active material can be minimized. Therefore, problems that may arise due to surface impurities, such as reduced battery capacity, increased interfacial resistance due to impeded lithium ion movement, gas generation due to impurity decomposition, and battery swelling, can be prevented. As a result, the capacity characteristics, high-temperature stability, and charge-discharge characteristics of rechargeable lithium batteries, including the positive electrode active material, can be improved. Here, the average particle size D of the core particles... 50 The particle size distribution can be obtained by randomly selecting approximately 20 particles from the scanning electron microscope image of the core particles, measuring the particle size (diameter, major axis, or major axis length), and then taking the size of the particles with a cumulative volume of 50% of the particle size distribution as the average particle size.
[0070] Core particles may include an average particle size D of about 9 μm to about 40 μm. 50 The first particle and the average particle size D of about 1 μm to about 8 μm 50 The second particle. Here, the first particle with a relatively large average particle size can be represented as a large particle, and the second particle with a relatively small average particle size can be represented as a small particle. Because the positive electrode active material includes both large and small particles, capacity and energy density can be maximized and long cycle life characteristics can be achieved.
[0071] The average particle size D of the first particle 50 It can be about 10 μm to about 38 μm, about 11 μm to about 35 μm, or about 12 μm to about 32 μm. Here, the average particle size D of the first particle is... 50 The particle size distribution can be obtained by randomly selecting approximately 20 particles from the scanning electron microscope image of the first particle, measuring the particle size (diameter, major axis, or major axis length), and then taking the size of the particles with a cumulative volume of 50% of the particle size distribution as the average particle size.
[0072] The average particle size D of the second particle 50 The particle size can be approximately 1.5 μm to approximately 7.5 μm, approximately 1.8 μm to approximately 7.2 μm, or approximately 2.0 μm to approximately 7.0 μm. Here, the average particle size D of the second particle... 50The particle size distribution can be obtained by randomly selecting approximately 20 particles from the scanning electron microscope image of the second particle, measuring the particle size (diameter, major axis, or major axis length), and then taking the size of the particles with a cumulative volume of 50% of the particle size distribution as the average particle size.
[0073] Coating layer
[0074] The coating layer is located on the surface of the core particle, and each coating layer comprises graphene with a layered structure of 2 to 50 layers. Using the coating layer, the adhesion strength and conductivity of the electrode plate can be ensured even when a small amount of binder and conductive material is used in the manufacture of the positive electrode. Furthermore, due to the reduced amount of binder or conductive material used in the manufacture of the positive electrode, the amount of positive electrode active material can be increased, enabling the rechargeable lithium battery to exhibit high capacity and high energy density characteristics. In addition, the coating layer has a layered structure exhibiting a dense crystalline structure, including crystalline carbon provided in a two-dimensional plane on the surface of the core particle, and can have a thin and uniform thickness. Therefore, the electronic conductivity of the positive electrode active material can be improved, the interfacial resistance can be reduced, lithium-ion intercalation and deintercalation can be performed more efficiently, and ionic conductivity can be improved because lithium ions diffuse along the layered structure.
[0075] A layered structure with 2 to 50 layers can be represented as a layered structure with 2 to 50 atomic layers. For example, the coating layer may include graphene with a layered structure having 2 to 48 layers, 5 to 45 layers, 7 to 40 layers, 10 to 35 layers, 15 to 35 layers, 20 to 35 layers, or 25 to 35 layers. The number of layers in the layered structure can be measured by high-resolution transmission electron microscopy (HR-TEM) images of the positive electrode active material particles.
[0076] The interlayer spacing d of the layered structure 002 The interlayer spacing d of the layered structure can be from about 0.320 nm to about 0.350 nm, for example, from about 0.325 nm to about 0.348 nm, from about 0.328 nm to about 0.345 nm, or from about 0.330 nm to about 0.342 nm. 002 Within these ranges, the positive electrode active material can further improve the adhesion strength and conductivity of the electrode plate. Here, the interlayer spacing d 002 It can be measured using methods known to those skilled in the art. For example, the interlayer spacing d of a layered structure can be measured as follows. 002The peaks on the (002) plane are obtained by X-ray diffraction (XRD) of the coating layer, and then the peaks on the (002) plane are analyzed. Here, the (002) plane represents the range of 25.0° < 2θ < 27.0°, where 2θ represents the diffraction angle. For example, the standard procedures equipped in the XRD apparatus can be used as data processing and analysis procedures to subject the XRD measurement data to noise reduction (baseline setting), etc. In addition, the peak profiles on the (002) plane can be fitted using standard fitting functions such as Gaussian functions, Lorentz functions, etc. Furthermore, the interlayer spacing d of the layered structure... 002 For example, this can be achieved by measuring the interlayer spacing d of graphite particles. 002 The method is used to represent the interlayer spacing d of the graphite particles. 002 The number of layers and the interlayer spacing (d) in a layered structure can be measured using XRD analysis of graphite microparticles. 002 The thickness of the coating layer and the total thickness of the coating layer were determined as average values, obtained by measurements taken at multiple randomly selected locations on the cross-section of the core particle via HR-TEM. Note that the relationships between these parameters follow the physical properties of the graphene coating layer, where the total thickness of the coating layer is the product of the number of layers and the average interlayer spacing.
[0077] The graphene coating may have a Raman spectral density of about 0.15 to about 0.50, for example about 0.15 to about 0.45, about 0.18 to about 0.45, or about 0.20 to about 0.40 at 1350 cm⁻¹. -1 Nearby peak intensity (I) D ) at 1580 cm -1 Nearby peak intensity (I) G The ratio of (I) D / I G When graphene's I D / I G Within these ranges, the positive electrode active material maximizes the adhesion strength and conductivity of the electrode plate. For example, Raman spectroscopy can be performed using a Raman spectrometer (e.g., ICRM7000 (Renishaw)) at a laser wavelength of approximately 632 nm and a wavelength of approximately 946 cm⁻¹. -1 The lowest Raman shift was measured. The peak intensity ratio described in this paper was obtained from approximately 946 cm⁻¹. -1 The peaks observed within the Raman shift range starting from the lowest Raman shift are obtained. These measurement conditions are standard in the art and will be within the capabilities of those skilled in the art as follows: adjusting these parameters, such as laser (laser) power or exposure time, while maintaining a relative trend in the peak intensity ratio to ensure reproducibility.
[0078] The graphene in the coating layer can be derived from graphite particles with an average size of less than or equal to about 2.5 μm. In this case, a coating layer of uniform thickness can be provided on the surface of the core particles, and thus, the adhesion strength of the positive electrode active material to the current collector and the conductivity of the electrode plate can be maximized. Furthermore, improving the structural stability of the positive electrode active material can effectively suppress side reactions with the electrolyte, reduce the amount of gas generated under high voltage and high temperature conditions, and achieve long cycle life characteristics.
[0079] When mixed with core particles, under the action of shear force, graphite microparticles including a considerable number of graphene layers can be delaminated to form a coating layer on the surface of the core particles, including a layered structure having about 2 to about 50 graphene layers.
[0080] Graphite microparticles can be plate-shaped. The average size D of graphite microparticles... 50 The average size of the graphite particles can be less than or equal to about 2.5 μm, for example, less than or equal to about 1.5 μm, less than or equal to about 1.0 μm, less than about 1 μm, less than or equal to about 0.8 μm, less than or equal to about 0.5 μm, less than or equal to about 0.4 μm, or less than or equal to about 0.3 μm, and can be greater than or equal to about 0.01 μm, greater than or equal to about 0.05 μm, greater than or equal to about 0.08 μm, or greater than or equal to about 0.1 μm. When the average size of the graphite particles is within these ranges, a coating layer of uniform thickness can be provided on the surface of the core particles, and the positive electrode active material can maximize the adhesion strength and conductivity of the electrode plate. Here, the average size D of the graphite particles... 50 It can be measured by a particle size analyzer and refers to the size of particles that account for 50% of the cumulative volume in the particle size distribution. Here, particle size can mean the length of the longest axis in a plane perpendicular to the thickness direction in a plate shape.
[0081] The thickness of the graphite microparticles can be less than or equal to about 1.0 μm, for example less than about 1 μm, less than or equal to about 0.9 μm, less than or equal to about 0.7 μm, or less than or equal to about 0.5 μm, and can be greater than or equal to about 0.01 μm, greater than or equal to about 0.05 μm, or greater than or equal to about 0.08 μm. When the thickness of the graphite microparticles is within these ranges, a coating layer of uniform thickness can be provided on the surface of the core particles, and the positive electrode active material can achieve maximized adhesion strength and conductivity of the electrode plate. Here, the thickness of the graphite microparticles can be measured by transmission electron microscopy of the graphite microparticles. Alternatively, the thickness of the graphite microparticles can be measured by transmission electron microscopy of a cross-section of the graphite microparticles cut by focused ion beam (FIB). However, this disclosure is not limited to this, and the thickness of graphite particles can be measured by, for example, SEM (scanning electron microscopy), TOF-SIMS (time-of-flight secondary ion mass spectrometry), XPS (X-ray photoelectron spectroscopy), AFM (atomic force microscopy) or EDS (energy dispersive spectroscopy), and can be measured by TEM-EDS (transmission electron microscopy-energy dispersive spectroscopy) line profile (line distribution).
[0082] Graphite microparticles may have a Raman spectral density of about 0.15 to about 0.50, for example about 0.15 to about 0.45, about 0.18 to about 0.45, or about 0.20 to about 0.40 at 1350 cm⁻¹. -1 Nearby peak intensity (I) D ) at 1580 cm -1 Nearby peak intensity (I) G The ratio of (I) D / I G When the I of graphite particles D / I G When the values are within these ranges, a coating layer of uniform thickness can be provided on the surface of the core particles, and the adhesion strength and conductivity of the electrode plates can be maximized.
[0083] Based on 100% by weight of total positive electrode active material, graphene may be included in the coating layer in amounts from about 0.02% to about 3.0% by weight, for example, from about 0.02% to about 2.8% by weight, from about 0.03% to about 2.5% by weight, from about 0.05% to about 2.0% by weight, from about 0.1% to about 2.0% by weight, from about 0.2% to about 2.0% by weight, from about 0.2% to about 1.0% by weight, or from about 0.2% to about 0.8% by weight. Here, the amount of graphene in the coating layer can be expressed as the amount of the coating layer. When the amount of graphene is within these ranges, the high capacity and high energy density characteristics of rechargeable lithium batteries can be improved, while also providing adhesion strength and conductivity of the electrode plates. Even if the amount of graphene is a very small amount, less than about 1% by weight, it can still coat the surface of the particles well, thereby increasing the electrical conductivity of the positive electrode active material, increasing lubrication, and increasing the density of the positive electrode.
[0084] In addition to graphene, the coating layer can further include carbon nanotubes. In this case, the energy density of the rechargeable lithium battery including the positive electrode active material is maximized because the particle (disc) density of the positive electrode active material is further improved. When the coating layer includes both graphene and carbon nanotubes, the powder resistance of the positive electrode active material can be further reduced, thereby maximizing the electrical conductivity of the positive electrode active material.
[0085] When the coating layer further includes carbon nanotubes, graphene can be sheet-shaped and coated on the surface of the core particle, and the carbon nanotubes can be firmly adhered to the sheet or its surface. That is, both graphene and carbon nanotubes can be uniformly coated on the surface of the core particle, which makes the positive electrode active material lubricating while maximizing electronic conductivity.
[0086] Graphene and carbon nanotubes can be composited (e.g., attached) to each other on a single planar surface. For example, when graphene is coated in a sheet shape on the surface of a core particle, fibrous carbon nanotubes can be located on the sheet-shaped graphene. In some instances, the positive electrode active material may include: a first coating layer on the surface of the core particle comprising a layered structure of graphene having 2 to 50 layers, and a second coating layer on the first coating layer comprising carbon nanotubes.
[0087] Carbon nanotubes may include at least one of single-walled carbon nanotubes (SWCNTs), thin-walled carbon nanotubes (TWCNTs), and multi-walled carbon nanotubes (MWCNTs).
[0088] The average length of carbon nanotubes can be from about 0.1 μm to about 35 μm, for example, from about 0.3 μm to about 30 μm, from about 0.5 μm to about 25 μm, from about 1 μm to about 20 μm, from about 3 μm to about 18 μm, or from about 5 μm to about 15 μm. When the average length of carbon nanotubes is within these ranges, a carbon coating layer of uniform thickness can be provided on the surface of the core particle, and the aggregate density and conductivity of the positive electrode active material can be maximized. Here, the length of the carbon nanotube refers to the length of the long axis passing through the center of the carbon nanotube unit. The average length of the carbon nanotubes can be obtained, for example, by randomly selecting about 20 carbon nanotubes from SEM or TEM images, measuring their lengths, and calculating the average value.
[0089] The average diameter of carbon nanotubes can be from about 1 nm to about 50 nm, for example, from about 1 nm to about 40 nm, from about 1.5 nm to about 30 nm, from about 1.8 nm to about 20 nm, or from about 2 nm to about 15 nm. Here, the diameter of a carbon nanotube refers to the length of its minor axis, which passes through the center of the carbon nanotube unit and is perpendicular to the major axis of the carbon nanotube. The average diameter of a carbon nanotube can be obtained, for example, by randomly selecting about 20 carbon nanotubes from a SEM or TEM image, measuring their diameters, and calculating the average value.
[0090] Based on 100% by weight of total positive electrode active material, carbon nanotubes with a carbon coating may be included in an amount from about 0.02% by weight to about 3.0% by weight, for example, from about 0.02% by weight to about 2.8% by weight, from about 0.03% by weight to about 2.5% by weight, from about 0.05% by weight to about 2.0% by weight, from about 0.05% by weight to about 1.0% by weight, from about 0.05% by weight to about 0.8% by weight, from about 0.05% by weight to about 0.5% by weight, from about 0.1% by weight to about 0.5% by weight, or from about 0.2% by weight to about 0.4% by weight. When the amount of carbon nanotubes in the carbon coating is within these ranges, the capacity and energy density of the rechargeable lithium battery can be improved.
[0091] When the coating layer further includes carbon nanotubes, based on a total of 100% by weight of the positive electrode active material, the carbon-coated graphene may be included in an amount from about 0.02% by weight to about 3.0% by weight, and the carbon nanotubes in the carbon-coated layer may also be included in an amount from about 0.02% by weight to about 3.0% by weight. For example, based on a total of 100% by weight of the positive electrode active material, the carbon-coated graphene may be included in an amount from about 0.05% by weight to about 2.0% by weight, and the carbon nanotubes may also be included in an amount from about 0.05% by weight to about 2.0% by weight. Furthermore, based on a total of 100% by weight of the positive electrode active material, the graphene may be included in an amount from about 0.05% by weight to about 0.5% by weight, and the carbon nanotubes may also be included in an amount from about 0.05% by weight to about 0.5% by weight. In addition, based on a total of 100% by weight of positive electrode active material, graphene may be included in an amount of about 0.05% by weight to about 0.1% by weight, and carbon nanotubes may be included in an amount of about 0.1% by weight to about 0.5% by weight.
[0092] The coating layer can be in the form of a film continuously surrounding the surface of the core particle, or, for example, in the form of a shell surrounding the entire surface of the core particle. This differs from structures in which only a portion of the surface of the core particle is coated. When the coating layer is provided to completely cover the surface of the core particle, the adhesion strength and conductivity of the electrode plate are maximized. Furthermore, the positive electrode active material exhibits improved structural stability without increasing resistance or reducing capacity, effectively suppresses side reactions with the electrolyte, reduces gas generation under high voltage and high temperature conditions, and provides long cycle life characteristics.
[0093] The thickness of the coating layer can be from about 3 nm to about 50 nm, for example, from about 3 nm to about 45 nm, from about 3 nm to about 40 nm, from about 3 nm to about 35 nm, from about 3 nm to about 30 nm, from about 4 nm to about 20 nm, or from about 5 nm to about 15 nm. When the thickness of the coating layer is within these ranges, the structural stability of the positive electrode active material can be improved, and side reactions with the electrolyte can be effectively suppressed without increasing resistance or decreasing capacity due to the coating layer. The thickness of the coating layer can be measured, for example, using transmission electron microscopy to examine the cross-section of the positive electrode active material particles cut by FIB (Focused Ion Beam). However, this disclosure is not limited to this, and the thickness of the coating layer can be measured by, for example, SEM, AFM, TOF-SIMS, XPS, or EDS analysis, and can be measured by TEM-EDS line profiling.
[0094] The coating layer can be thin, ranging from approximately a few nanometers to tens of nanometers in thickness, but it remains uniform in thickness. For example, the difference between the highest and lowest thicknesses of the coating layer can be less than or equal to about 30 nm, for example, less than or equal to about 25 nm, less than or equal to about 20 nm, or less than or equal to about 15 nm and greater than or equal to about 0.30 nm, greater than or equal to about 0.33 nm, greater than or equal to about 0.35 nm, or greater than or equal to about 0.40 nm. A difference between the highest and lowest thicknesses of the coating layer satisfying these ranges means that a coating layer of uniform thickness is provided on the surface of the positive electrode active material particles in the form of a film. This maximizes the adhesion strength and conductivity of the electrode plate. Here, the highest and lowest thicknesses of the coating layer can be measured based on electron microscopy images of the positive electrode active material. For example, in an electron microscopy image of a cross-section of the positive electrode active material particles, the thickness of the thickest portion of the cross-section of the coating layer can be defined as the highest thickness of the coating layer, and the thickness of the thinnest portion can be defined as the lowest thickness of the coating layer. The thickness of the coating layer can be the vertical distance from the outer surface of the core particle to the outer surface of the coating layer. A scanning electron microscope or a transmission electron microscope can be used as the electron microscope.
[0095] Methods for preparing positive electrode active materials
[0096] Methods for preparing positive electrode active materials according to some exemplary embodiments include: preparing (preparing) core particles comprising a lithium transition metal complex; preparing particles having an average size D of less than or equal to about 2.5 μm. 50 Graphite microparticles; and dry mixing (dry mixing) of core particles and graphite microparticles to obtain positive electrode active material.
[0097] In a method for preparing the positive electrode active material according to some exemplary embodiments, graphite microparticles can be used to provide a carbon coating layer comprising a layered structure of graphene having 2 to 50 layers on the surface of the core particle. Therefore, while minimizing manufacturing costs, the adhesion strength and conductivity of the electrode plate can be ensured, even when small amounts of binder and conductive materials are used during the manufacture of the positive electrode. Furthermore, since the amount of binder used in the manufacture of the positive electrode is reduced, the amount of positive electrode active material can be increased, enabling the rechargeable lithium battery including the positive electrode active material to possess high capacity and high energy density characteristics.
[0098] The method for preparing the positive electrode active material according to the example embodiments is described in detail below.
[0099] Preparation of core particles
[0100] Preparation (Preparation) of core particles comprising lithium transition metal complexes. Since the core particles can be prepared as described above, their detailed description is omitted.
[0101] Preparation of graphite microparticles
[0102] Prepare materials with an average size D of less than or equal to about 2.5 μm. 50 Graphite microparticles. Specific properties of graphite microparticles, such as average size and I... D / I G The value can be the same as that of the graphite particles in the above-mentioned positive electrode active material, and therefore, its detailed description is omitted.
[0103] In this process, an average size D of about 1 μm to about 25 μm, for example about 2 μm to about 25 μm or about 3 μm to about 25 μm can be produced. 50 Flake graphite was pulverized to prepare a sample with an average size D of less than or equal to about 2.5 μm. 50 Graphite microparticles. The average size D of flake graphite. 50 The size of the flake graphite can be less than or equal to about 20 μm, less than or equal to about 18 μm, less than or equal to about 15 μm, less than or equal to about 12 μm, or less than or equal to about 10 μm, and can be greater than or equal to about 4 μm, greater than or equal to about 5 μm, or greater than or equal to about 6 μm. The average size of the flake graphite can be measured from scanning electron microscope images. The average size D of the flake graphite 50 It can be measured using a particle size analyzer and refers to the size of particles that have a cumulative volume of 50% in the particle size distribution. Particle size refers to the length of the longest axis in a plane perpendicular to the thickness direction in a plate shape.
[0104] Flake graphite may have a Raman spectroscopy intensity of greater than or equal to about 0.01 and less than about 0.15, for example, about 0.02 to about 0.14, about 0.08 to about 0.14, or about 0.1 to about 0.14 at 1350 cm⁻¹. -1 Nearby peak intensity (I) D ) at 1580 cm -1 Nearby peak intensity (I) G The ratio of (I) D / I G ).
[0105] The pulverization of flake graphite can be carried out, for example, using a grinding process. The grinding process can use methods known to those skilled in the art, and can utilize apparatus such as ball mills, bead mills, spray mills, pin mills, roller mills, mixing mills, colloid mills, or air classifiers (ACMs).
[0106] Flake graphite can be pulverized using ball milling, and zirconia beads with a size of about 1 mm to about 25 mm can be used for ball milling at a speed of about 200 rpm to about 5,000 rpm for about 30 minutes to about 4 hours. The size of the zirconia beads used for pulverizing flake graphite can be about 1.2 mm to about 23 mm, about 1.3 mm to about 21 mm, or about 1.5 mm to about 20 mm. Pulverization of flake graphite can be carried out at speeds of about 250 rpm to about 4,500 rpm, about 300 rpm to about 4,000 rpm, about 400 rpm to about 3,000 rpm, or about 500 rpm to about 2,000 rpm. Alternatively, pulverization of flake graphite can be carried out for about 30 minutes to about 3 hours or about 30 minutes to about 2 hours. When the bead size, stirring speed, or stirring time are within these ranges, the particle size of the graphite particles can be controlled to a desired level.
[0107] Obtaining positive electrode active material
[0108] Core particles and graphite microparticles are mixed to prepare the positive electrode active material. In this process, crystalline carbon derived from graphite microparticles coats the surface of the core particles, thereby providing a coating layer comprising a layered graphene structure having 2 to 50 layers on the surface of the core particles. Because the coating layer is provided on the surface of the core particles with a thin and uniform thickness in this process, the adhesion strength and conductivity of the electrode plate are ensured even when using small amounts of binder and conductive material. Furthermore, due to the reduced amount of binder and conductive material, the amount of positive electrode active material can be increased, enabling the rechargeable lithium battery to possess high capacity and high energy density characteristics. The coating layer provided in this process is the same as the coating layer in the positive electrode active material described above, and therefore its detailed description is omitted.
[0109] Based on a total amount of 100% by weight of core particles and graphite microparticles, the graphite microparticles can be mixed in amounts from about 0.02% by weight to about 3.0% by weight, for example, from about 0.02% by weight to about 2.8% by weight, from about 0.03% by weight to about 2.5% by weight, from about 0.05% by weight to about 2.0% by weight, from about 0.1% by weight to about 2.0% by weight, from about 0.2% by weight to about 2.0% by weight, from about 0.2% by weight to about 1.0% by weight, or from about 0.2% by weight to about 0.8% by weight. When the amount of graphite microparticles mixed in these ranges, the adhesion strength and conductivity of the electrode plates can be improved, while the high capacity and high energy density characteristics of the rechargeable lithium battery can be improved. Even if the amount of graphite microparticles is less than about 1% by weight, graphene can be well coated on the surface of the core particles, thereby increasing the electrical conductivity of the positive electrode active material, increasing lubrication, and increasing the density of the positive electrode.
[0110] This process can be carried out by mixing core particles and graphite microparticles and applying shear force. In this case, a coating layer comprising graphene having a layered structure exhibiting a dense crystalline structure can be provided, while crystalline carbon derived from graphite microparticles is located in a two-dimensional plane on the surface of the core particles. The process can be carried out, for example, using a device for applying shear force, such as a device having blades internally. However, this disclosure is not limited in this respect.
[0111] This process of mixing core particles and graphite microparticles can be performed using a dry mixer (dry mixer). The core particles and graphite microparticles can be mixed at approximately 1,000 s. -1 From approximately 9,000 s -1 The shear rate is mixed with a blade rotation speed of less than or equal to about 20 m / s.
[0112] Core particles and graphite microparticles can reach approximately 1,500 s. -1 From approximately 8,800 s -1 Approximately 2,000 s -1 From approximately 8,800 s -1 Or approximately 2,500 s -1 From approximately 8,500 s -1 The shear rates are mixed. When the shear rates are within these ranges, a carbon coating layer can be effectively provided on the surface of the core particles without damaging the core particles.
[0113] The rotational speed of the blades within the device for applying shear force can be less than or equal to about 18 m / s, less than or equal to about 15 m / s, or less than or equal to about 10 m / s and greater than or equal to about 3 m / s, greater than or equal to about 4 m / s, or greater than or equal to about 5 m / s. When the rotational speed of the blades is within these ranges, a coating layer can be effectively provided on the surface of the core particle without damaging the core particle.
[0114] In this process, core particles and graphite microparticles can be mixed at speeds of approximately 500 rpm to approximately 6,000 rpm, for example, at speeds of approximately 600 rpm to approximately 5,500 rpm, approximately 700 rpm to approximately 5,000 rpm, or approximately 800 rpm to approximately 4,000 rpm. When the mixing conditions are within these ranges, a coating layer can be effectively provided on the surface of the core particles without damaging the core particles.
[0115] Core particles and graphite microparticles can be dry-mixed. This reduces manufacturing costs, and because the coating is thin and uniform, the adhesion strength and conductivity of the electrode plates can be further improved. Here, "dry" means a state without intentional contact with solvents, such as process solvents, or a state without intentionally including solvents. Dry mixing can be performed using methods known to those skilled in the art, such as dry mixers (Nobilta mixers), homogenizers, or Henschel mixers.
[0116] In obtaining the positive electrode active material, carbon nanotubes can be further mixed with core particles and graphite microparticles. In this case, graphene can be sheet-coated on the surface of the core particles, and carbon nanotubes can be firmly adhered to the sheet or the surface of the sheet. Providing a coating layer including both graphite microparticles and carbon nanotubes on the surface of the core particles can reduce the powder resistance of the positive electrode active material and improve its particle density and electrical conductivity.
[0117] When further mixing carbon nanotubes, the method may further include preparing carbon nanotubes with an average length of about 0.1 μm to about 35 μm by pulverizing carbon nanotube raw materials having an average length greater than or equal to about 40 μm. For example, the average length of the carbon nanotube raw material may be greater than or equal to about 40 μm, greater than or equal to about 45 μm, or greater than or equal to about 50 μm, and may be less than or equal to about 100 μm, less than or equal to about 95 μm, or less than or equal to about 90 μm, and may be about 40 μm to about 100 μm, about 45 μm to about 100 μm, about 50 μm to about 100 μm, or about 50 μm to about 90 μm. Here, the length of the carbon nanotube raw material refers to the length of the long axis passing through the center of the carbon nanotube raw material unit. For example, the average length of the carbon nanotube raw material can be obtained by randomly selecting about 20 carbon nanotube raw materials from SEM or TEM images, measuring the length, and calculating the average value.
[0118] Grinding processes can be used to pulverize carbon nanotube raw materials. Grinding processes can employ methods known to those skilled in the art. For example, grinding processes can utilize apparatus such as ball mills, bead mills, spray mills, pin mills, roller mills, mixing mills, colloid mills, or air classifiers (ACMs).
[0119] Carbon nanotube raw materials can be pulverized using ball milling, and zirconia beads with a size of about 1 mm to about 25 mm can be used for ball milling at a speed of about 200 rpm to about 5,000 rpm for about 30 minutes to about 4 hours. The size of the zirconia beads used for pulverizing the carbon nanotube raw materials can be about 1.2 mm to about 23 mm, about 1.3 mm to about 21 mm, or about 1.5 mm to about 20 mm. The pulverization of the carbon nanotube raw materials can be carried out at speeds of about 250 rpm to about 4,500 rpm, about 300 rpm to about 4,000 rpm, about 400 rpm to about 3,000 rpm, or about 500 rpm to about 2,000 rpm. Furthermore, the pulverization of the carbon nanotube raw materials can be carried out for about 30 minutes to about 3 hours or about 30 minutes to about 2 hours. When the bead size, stirring speed, or stirring time are within these ranges, the size of the carbon nanotubes can be controlled to the desired level.
[0120] The preparation of carbon nanotubes can be carried out separately from the steps described above for preparing graphite microparticles, and in the step of obtaining the positive electrode active material, the pulverized graphite microparticles and the pulverized carbon nanotubes can be added separately. Alternatively, carbon nanotubes can be prepared during the step of preparing graphite microparticles by combining carbon nanotube raw materials having an average length greater than or equal to about 40 μm with an average size D of about 3 μm to about 25 μm. 50 The flake graphite is co-crushed together. In this case, graphite particles and carbon nanotubes can be combined with each other, making it possible to prepare coated raw materials, and in the positive electrode active material, both the graphene coating and the carbon nanotube coating can be in a single sheet plane.
[0121] When carbon nanotubes are further mixed, based on a total of 100 wt% core particles, graphite microparticles, and carbon nanotubes, the graphite microparticles can be mixed in amounts from about 0.02 wt% to about 3.0 wt%, for example, from about 0.02 wt% to about 2.8 wt%, from about 0.03 wt% to about 2.5 wt%, from about 0.05 wt% to about 2.0 wt%, from about 0.05 wt% to about 1.0 wt%, from about 0.05 wt% to about 0.8 wt%, from about 0.05 wt% to about 0.5 wt%, or from about 0.05 wt% to about 0.1 wt%. When the amount of graphite microparticles is within these ranges, the aggregate density and conductivity of the positive electrode active material can be improved, and the rechargeable lithium battery including the positive electrode active material can exhibit high capacity and high energy density characteristics. Even when the amount of graphite microparticles is less than about 1 wt%, graphene can be well coated on the surface of the core particles, thereby increasing the electrical conductivity of the positive electrode active material and increasing the density of the positive electrode.
[0122] Based on a total of 100 wt% of core particles, graphite microparticles, and carbon nanotubes, the carbon nanotubes can be mixed in amounts from about 0.02 wt% to about 3.0 wt%, for example, from about 0.02 wt% to about 2.8 wt%, from about 0.03 wt% to about 2.5 wt%, from about 0.05 wt% to about 2.0 wt%, from about 0.05 wt% to about 1.0 wt%, from about 0.05 wt% to about 0.8 wt%, from about 0.05 wt% to about 0.5 wt%, from about 0.1 wt% to about 0.5 wt%, or from about 0.2 wt% to about 0.4 wt%. When the amount of carbon nanotubes is within these ranges, the aggregate density and conductivity of the positive electrode active material can be improved, and the rechargeable lithium battery including the positive electrode active material can have high capacity and high energy density characteristics. Even if the amount of carbon nanotubes is less than about 1 wt%, the carbon nanotubes can be well coated on the surface of the core particles, thereby increasing the electrical conductivity of the positive electrode active material and increasing the density of the positive electrode.
[0123] positive electrode
[0124] In an embodiment, the positive electrode includes a current collector and a layer of positive electrode active material on the current collector, wherein the positive electrode active material layer includes the aforementioned positive electrode active material. In addition to the aforementioned positive electrode active material, the positive electrode active material layer may further include other types of positive electrode active materials. Based on a total of 100% by weight of the positive electrode active material layer, the positive electrode active material may be included in amounts of approximately 60% to approximately 99.9% by weight, approximately 70% to approximately 99.9% by weight, approximately 80% to approximately 99.9% by weight, approximately 90% to approximately 99.9% by weight, or approximately 95% to approximately 99.9% by weight.
[0125] The configuration of the positive electrode according to some embodiments is described in detail below.
[0126] current collector
[0127] There are no restrictions on the current collector, as long as it is conductive and does not cause undesirable chemical changes to the positive electrode including the current collector and the rechargeable lithium battery. For example, the current collector may include thin films of aluminum (Al), stainless steel (SUS), indium (In), magnesium (Mg), titanium (Ti), iron (Fe), cobalt (Co), nickel (Ni), zinc (Zn), germanium (Ge), lithium (Li), or combinations thereof.
[0128] The current collector can be in the form of, for example, a plate, thin sheet, membrane, sheet, foil, mesh, porous body, foam, or nonwoven material. Microscopic irregularities can be incorporated into the current collector's surface, which can improve the adhesion strength to the positive electrode active material.
[0129] The thickness of the current collector can be from about 1 μm to about 20 μm, for example from about 5 μm to about 15 μm or from about 7 μm to about 10 μm.
[0130] The positive electrode active material layer may further include a binder, a conductive material, or a combination thereof.
[0131] adhesive
[0132] The binder is used to adhere the positive electrode active material particles to each other and to adhere the positive electrode active material to the current collector. The binder may include one or more of polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, polymers including ethylene oxide (including polymers of ethylene oxide), polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, epoxy resin, (meth)acrylate resin, polyester resin, polyacrylonitrile, and nylon. However, this disclosure is not limited to these examples.
[0133] Based on a total of 100% by weight of the positive electrode active material layer, the binder may be included in an amount from about 0.1% by weight to about 1.5% by weight, for example less than or equal to about 1.3% by weight, less than or equal to about 1.0% by weight, or less than or equal to about 0.9% by weight.
[0134] conductive materials
[0135] Conductive materials are used to provide conductivity to the electrodes, and any material that does not cause undesirable chemical changes and is electronically conductive can be used in the battery. Conductive materials may include, for example, carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers, carbon nanotubes, etc.; metal-based materials including metal powders or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0136] Based on a total of 100% by weight of the positive electrode active material layer, conductive material may be included in amounts from 0 to approximately 3% by weight, for example from approximately 0.05% to approximately 3% by weight, less than or equal to approximately 2.5% by weight, less than or equal to approximately 2.0% by weight, less than or equal to approximately 1.0% by weight, less than or equal to approximately 0.8% by weight, less than or equal to approximately 0.7% by weight, or less than or equal to approximately 0.5% by weight. Because the positive electrode active material layer includes the aforementioned positive electrode active material, it can exhibit excellent electronic conductivity and low resistivity and high density even if it does not contain conductive material alone or contains a very small amount of conductive material.
[0137] The density of the positive electrode active material layer can be from about 2.0 g / cc to about 6.0 g / cc, for example, from about 2.3 g / cc to about 5.8 g / cc, from about 2.5 g / cc to about 5.7 g / cc, or from about 2.5 g / cc to about 5.5 g / cc. When the lithium transition metal composite compound of the core particles is a lithium cobalt-based oxide, the density of the positive electrode active material layer can be from about 3.5 g / cc to about 5.0 g / cc, from about 3.7 g / cc to about 4.9 g / cc, from about 3.8 g / cc to about 4.8 g / cc, or from about 4.0 g / cc to about 4.5 g / cc. When the density of the positive electrode active material layer is within these ranges, the energy density of the rechargeable lithium battery can be improved. In particular, because the aforementioned positive electrode active material has high particle strength and provides good lubrication on the particle surface, compression processing can be performed under higher pressures. In addition, due to the high lubrication on the surface of the positive electrode active material, the compression efficiency of the positive electrode can be increased through the sliding effect. In addition, because the compression process can be carried out under higher pressure, the pores in the positive electrode active material layer of the electrode plate can be reduced, and the density of the positive electrode active material layer can be further improved.
[0138] The adhesion strength of the positive electrode active material layer to the current collector can be greater than or equal to about 0.5 gf / mm, and the resistivity of the positive electrode active material layer can be less than or equal to about 40 Ω·cm. For example, the adhesion strength of the positive electrode active material layer to the current collector can be greater than or equal to about 1.0 gf / mm, greater than or equal to about 1.5 gf / mm, greater than or equal to about 2.0 gf / mm, or greater than or equal to about 2.5 gf / mm, and can be less than or equal to about 30 gf / mm, less than or equal to about 28 gf / mm, less than or equal to about 25 gf / mm, or less than or equal to about 23 gf / mm. Furthermore, the resistivity of the positive electrode active material layer can be less than or equal to about 35 Ω·cm, less than or equal to about 30 Ω·cm, less than or equal to about 25 Ω·cm, or less than or equal to about 20 Ω·cm, and can be greater than or equal to about 0.5 Ω·cm, greater than or equal to about 1.0 Ω·cm, greater than or equal to about 3.0 Ω·cm, greater than or equal to about 5.0 Ω·cm, or greater than or equal to about 5.5 Ω·cm. Because the positive electrode active material layer includes the aforementioned positive electrode active material, even if it does not contain a separate conductive material or contains a very small amount of conductive material, the positive electrode active material layer can exhibit excellent electronic conductivity and achieve low resistivity, and can provide high electrode plate adhesion strength even with the use of a small amount of binder.
[0139] The porosity of the positive electrode can be less than or equal to about 30%, less than or equal to about 25%, less than or equal to about 20% and greater than or equal to about 1%, greater than or equal to about 5%, or greater than or equal to about 7%. When the porosity of the positive electrode is within these ranges, the capacity and energy density of the positive electrode can be improved. Here, the porosity of the positive electrode refers to the ratio of the volume of pores present within the positive electrode to the total volume of the positive electrode. Porosity can be measured, for example, by mercury porosimetry (mercury porosimetry).
[0140] Rechargeable lithium batteries
[0141] A rechargeable lithium battery according to an example embodiment includes: a positive electrode comprising a current collector and a positive electrode active material layer on the current collector, wherein the positive electrode active material layer comprises the aforementioned positive electrode active material; a negative electrode; and an electrolyte. The rechargeable lithium battery may be a lithium-ion battery using a liquid electrolyte, or an all-solid-state rechargeable lithium battery or a semi-solid-state rechargeable lithium battery using a solid electrolyte. The configuration of the lithium-ion battery is described in detail below.
[0142] Rechargeable lithium batteries can be cylindrical, prismatic, pouch-shaped, or coin-shaped, depending on their shape. Figure 1 A schematic diagram showing a cross-section of a cylindrical rechargeable lithium battery cut along a vertical axis and an electrode assembly 40 extending therefrom. Figure 2 This is a cross-sectional view of a prismatic rechargeable lithium battery, and Figure 3 and 4 This is a schematic exploded perspective view of a pouch-type rechargeable lithium battery. (Refer to...) Figures 1 to 4 The rechargeable lithium battery 100 includes an electrode assembly 40 and a housing 50. The electrode assembly 40 has a separator 30 between a positive electrode 10 and a negative electrode 20, and the electrode assembly 40 is housed in the housing 50. The positive electrode 10, the negative electrode 20, and the separator 30 may be impregnated with an electrolyte solution (not shown).
[0143] like Figure 1 As shown, the rechargeable lithium battery 100 may include a sealing member 60 of the sealed housing 50. Figure 2 As shown, the rechargeable lithium battery 100 may include a positive electrode lead terminal 11, a positive electrode terminal 12, a negative electrode lead terminal 21, and a negative electrode terminal 22. The rechargeable lithium battery 100 may include electrode terminals 70 forming electrical paths for conducting current supplied in the electrode assembly 40. The electrode terminals 70 may be as follows: Figure 4 They can be arranged in the same direction as in the middle, or the positive electrode terminal 71 and the negative electrode terminal 72 can be arranged as follows: Figure 3 It is set in the opposite direction as in the middle.
[0144] negative electrode
[0145] The negative electrode may include a current collector and a negative electrode active material layer on the current collector. The negative electrode active material layer includes a negative electrode active material, and may further include a binder, a conductive material, or a combination thereof.
[0146] Negative electrode active material
[0147] The negative electrode active material includes a material capable of reversibly intercalating / deintercalating lithium ions, lithium metal, an alloy of lithium metal, a material capable of doping and dedoping lithium, or a transition metal oxide.
[0148] The material capable of reversibly intercalating / deintercalating lithium ions may include carbon-based materials such as crystalline carbon, amorphous carbon, or a combination thereof. The crystalline carbon may be irregular or flake-like, scaly, spherical or fibrous natural graphite or artificial graphite. The amorphous carbon may be soft carbon, hard carbon, mesophase pitch carbonized product, calcined coke and the like.
[0149] As the alloy of lithium metal, an alloy of lithium and a metal selected from Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al and Sn may be used.
[0150] The material capable of doping and dedoping lithium may be a Si-based negative electrode active material or a Sn-based negative electrode active material. The Si-based negative electrode active material may be silicon, a silicon-carbon composite, SiO x (0<x≤2), a Si-Q alloy, or a combination thereof. In the formula Si-Q, Q is an alkali metal, an alkaline earth metal, a Group 13 element, a Group 14 element (excluding Si), a Group 15 element, a Group 16 element, a transition metal, a rare earth element, or a combination thereof, and for example Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po, or a combination thereof. The Sn-based negative electrode active material may be Sn, SnO2, a Sn-based alloy, or a combination thereof.
[0151] The silicon-carbon composite may be a composite of silicon and amorphous carbon. The average particle diameter D of the silicon-carbon composite particles 50may be, for example, about 0.5 μm to about 20 μm. According to some embodiments, the silicon-carbon composite may be in the form of silicon particles and amorphous carbon coated on the surfaces of the silicon particles. The silicon-carbon composite may include secondary particles (core) in which silicon primary particles are aggregated, and an amorphous carbon coating layer (shell) on the surfaces of the secondary particles. Amorphous carbon may also be present between the silicon primary particles, for example, the silicon primary particles may be coated with amorphous carbon. The secondary particles may be dispersed in an amorphous carbon matrix.
[0152] The silicon-carbon composite may further include crystalline carbon. For example, the silicon-carbon composite may include: a core comprising crystalline carbon and silicon particles, and an amorphous carbon coating layer on the surface of the core. The crystalline carbon may be artificial graphite, natural graphite, or a combination thereof. The amorphous carbon may include soft carbon, hard carbon, mesophase pitch carbonized product, calcined coke, and the like.
[0153] When the silicon-carbon composite includes silicon and amorphous carbon, based on 100 wt% of the silicon-carbon composite, the amount of silicon may be about 10 wt% to about 50 wt%, and the amount of amorphous carbon may be about 50 wt% to about 90 wt%. In addition, when the silicon-carbon composite includes silicon, amorphous carbon and crystalline carbon, based on 100 wt% of the silicon-carbon composite, the amount of silicon may be about 10 wt% to about 50 wt%, the amount of crystalline carbon may be about 10 wt% to about 70 wt%, and the amount of amorphous carbon may be about 20 wt% to about 40 wt%.
[0154] The thickness of the amorphous carbon coating layer may be about 5 nm to about 100 nm. The average particle diameter D of the silicon particles (primary particles) 50 may be about 10 nm to about 1 μm or about 10 nm to about 200 nm. The silicon particles may exist as elemental silicon, in the form of a silicon alloy, or in an oxidized form. The oxidized form of silicon may be represented as SiO x (0<x≤2). At this time, the atomic content ratio of Si:O indicating the oxidation degree may be about 99:1 to about 33:67.
[0155] The Si-based negative electrode active material or Sn-based negative electrode active material may be mixed with the carbon-based negative electrode active material. When the Si-based negative electrode active material or Sn-based negative electrode active material is used in combination with the carbon-based negative electrode active material, the weight ratio of the Si-based negative electrode active material or Sn-based negative electrode active material to the carbon-based negative electrode active material may be about 1:99 to about 90:10.
[0156] Based on 100 wt% of the total negative electrode active material layer, the negative electrode active material may be included in an amount of about 80 wt% to about 99 wt%, for example, about 85 wt% to about 99 wt%, or about 90 wt% to about 99 wt%.
[0157] adhesive
[0158] The binder is used to adhere the negative electrode active material particles to each other, and also to adhere the negative electrode active material to the current collector. The binder may be a non-aqueous binder, an aqueous binder, a dry binder, or a combination thereof.
[0159] Non-aqueous adhesives may include polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene-propylene copolymer, polystyrene, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, polyamide-imide, polyimide, or combinations thereof.
[0160] Waterborne adhesives may include styrene-butadiene rubber, (meth)acrylated styrene-butadiene rubber, (meth)acrylonitrile-butadiene rubber, (meth)acrylic rubber, butyl rubber, fluororubber, polyethylene oxide, polyvinylpyrrolidone, polyepoxygenated alcohol, polyphosphazene, poly(meth)acrylonitrile, ethylene propylene diene copolymer, polyvinylpyridine, chlorosulfonated polyethylene, latex, polyester resin, (meth)acrylic resin, phenolic resin, epoxy resin, polyvinyl alcohol, or combinations thereof.
[0161] When an aqueous binder is used as the negative electrode binder, it may further include a cellulose-based compound capable of imparting viscosity. As a cellulose-based compound, one or more of carboxymethyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, or their alkali metal salts may be mixed and used. The alkali metal may be Na, K, or Li.
[0162] Dry adhesives can be polymeric materials that can be turned into fibers, and can be, for example, polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyethylene oxide, or combinations thereof.
[0163] Based on 100% by weight of the total negative electrode active material layer, the binder may be included in an amount of about 0.5% by weight to about 5% by weight, for example, about 0.5% by weight to about 4% by weight or about 1% by weight to about 3% by weight.
[0164] conductive materials
[0165] Conductive materials are included to provide electrode conductivity, and any electrically conductive material can be used as the conductive material unless it causes undesirable chemical changes. Examples of conductive materials include carbon-based materials such as natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fibers, carbon nanofibers, carbon nanotubes, etc.; metal-based materials including metal powders or metal fibers of copper, nickel, aluminum, silver, etc.; conductive polymers such as polyphenylene derivatives; or mixtures thereof.
[0166] Based on 100% by weight of the total negative electrode active material layer, conductive material may be included in an amount of about 0.5% by weight to about 5% by weight, for example, about 0.5% by weight to about 4% by weight or about 1% by weight to about 3% by weight.
[0167] current collector
[0168] There are no particular restrictions on the negative electrode current collector, as long as it does not cause undesirable chemical changes in the negative electrode and the rechargeable lithium battery including the negative electrode. The negative electrode current collector can be, for example, copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, or a combination thereof.
[0169] The negative electrode current collector can be in the form of, for example, a plate, thin sheet, membrane, sheet, foil, mesh, porous body, foam, or nonwoven material. The negative electrode current collector may include microscopic irregularities on its surface, which can improve the adhesion strength to the negative electrode active material.
[0170] The thickness of the negative electrode current collector can be from about 1 μm to about 20 μm, for example from about 5 μm to about 15 μm or from about 7 μm to about 10 μm.
[0171] electrolytes
[0172] The electrolyte used in rechargeable lithium batteries may be an electrolyte solution, which may include non-aqueous organic solvents and lithium salts.
[0173] Non-aqueous organic solvents are used as media for transporting ions that participate in the electrochemical reactions of a battery. Non-aqueous organic solvents can be carbonate (carbonate-based) solvents, ester (ester-based) solvents, ether (ether-based) solvents, ketone (ketone-based) solvents, alcohol (alcohol-based) solvents, aprotic solvents, or combinations thereof.
[0174] Carbonate solvents may include dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC), ethylene carbonate (EC), propylene carbonate (PC), butyl carbonate (BC), etc.
[0175] Ester solvents may include methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, decanoic acid lactone, mevalonate lactone, caprolactone, etc.
[0176] Ether solvents may include dibutyl ether, tetraethylene glycol dimethyl ether, diethylene glycol dimethyl ether, dimethoxyethane, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, tetrahydrofuran, etc.
[0177] Ketone solvents may include cyclohexanone, etc. Alcohol solvents may include ethanol, isopropanol, etc., and aprotic solvents may include nitriles such as R-CN (where R is a C2 to C20 straight-chain, branched, or cyclic hydrocarbon group, and may include double bonds, aromatic rings, or ether groups, etc.); amides such as dimethylformamide; dioxolane such as 1,3-dioxolane, 1,4-dioxolane, etc.; sulfolane, etc.
[0178] Non-aqueous organic solvents may be used alone or in mixtures of two or more types, and when two or more types are used in mixtures, the mixing ratio may be appropriately adjusted according to the desired battery performance, as is known to those skilled in the art.
[0179] When using carbonate solvents, cyclic carbonates and chain carbonates can be mixed and used together, and cyclic carbonates and chain carbonates can be mixed in a volume ratio of about 1:1 to about 1:9.
[0180] Non-aqueous organic solvents may further include aromatic hydrocarbon organic solvents. For example, carbonate solvents and aromatic hydrocarbon organic solvents may be mixed and used in a volume ratio of about 1:1 to about 30:1.
[0181] The electrolyte solution may further include vinylene carbonate, vinylene carbonate, or ethylene carbonate compounds to improve battery cycle life.
[0182] Examples of ethylene carbonate compounds include fluoroethylene carbonate, difluoroethylene carbonate, chloroethylene carbonate, dichloroethylene carbonate, bromoethylene carbonate, dibromoethylene carbonate, nitroethylene carbonate, and cyanoethylene carbonate.
[0183] Lithium salts dissolved in organic solvents supply lithium ions in the battery, enabling basic operation of rechargeable lithium batteries and improving lithium ion transport between the positive and negative electrodes. Examples of lithium salts may include those selected from LiPF6, LiBF4, LiSbF6, LiAsF6, LiClO4, LiAlO2, LiAlCl4, LiPO2F2, LiCl, LiI, LiN(SO2C2F5)2, Li(FSO2)2N (lithium bis(fluorosulfonyl)imide; LiFSI), LiC4F9SO3, LiN(C x F 2x+1 SO2)(C y F 2y+1 One or more of the following: SO2 (where x and y are integers from 1 to 20), lithium trifluoromethanesulfonate, lithium tetrafluoroethanesulfonate, lithium difluorobis(oxalate)phosphate (LiDFBOP), and lithium bis(oxalate)borate (LiBOB).
[0184] The concentration of lithium salt can be in the range of about 0.1 M to about 2.0 M. When the concentration of lithium salt is in this range, the electrolyte solution has suitable ionic conductivity and viscosity, and therefore excellent performance can be achieved and lithium ions can move efficiently.
[0185] diaphragm
[0186] Depending on the type of rechargeable lithium battery, the rechargeable lithium battery may further include a separator between the positive and negative electrodes. The separator may include, for example, a multilayer membrane of polyethylene, polypropylene, polyvinylidene fluoride, or two or more layers thereof, and may include hybrid multilayer membranes such as a polyethylene / polypropylene two-layer separator, a polyethylene / polypropylene / polyethylene three-layer separator, a polypropylene / polypropylene / polypropylene three-layer separator, etc.
[0187] The diaphragm may include a porous substrate and a coating on one or both surfaces of the porous substrate, comprising organic materials, inorganic materials, or combinations thereof.
[0188] The porous substrate may be a polymer film formed from any of the following polymers: polyolefins such as polyethylene and polypropylene, polyesters such as polyethylene terephthalate, polybutylene terephthalate and polyethylene naphthalate, polyacetal, polyamide, polyimide, polycarbonate, polyetherketone, polyaryletherketone, polyetherimide, polyamideimide, polybenzimidazole, polyethersulfone, polyphenylene ether, cyclic olefin copolymers, polyphenylene sulfide, and polytetrafluoroethylene (PTFE; Teflon®) or copolymers or mixtures thereof. The porous substrate may include glass fiber, or may include a composite film of polymer and glass fiber.
[0189] The porous substrate may have a thickness of about 1 μm to about 40 μm, for example, about 1 μm to about 30 μm, about 1 μm to about 20 μm, about 5 μm to about 15 μm, or about 10 μm to about 15 μm.
[0190] Organic materials may include (meth)acrylic acid copolymers, which include a first structural unit and a second structural unit, wherein the first structural unit is derived from (meth)acrylamide, and the second structural unit includes at least one structural unit derived from (meth)acrylic acid or (meth)acrylate and a structural unit derived from (meth)acryloylsulfamic acid or a salt thereof.
[0191] Inorganic materials may include inorganic particles selected from Al2O3, SiO2, TiO2, SnO2, CeO2, MgO, NiO, CaO, Ga2O3, ZnO, ZrO2, Y2O3, SrTiO3, BaTiO3, Mg(OH)2, boehmite, and combinations thereof, but this disclosure is not limited thereto. The average particle size D of the inorganic particles...50 It can be from about 1 nm to about 2000 nm, for example from about 100 nm to about 1000 nm, or from about 100 nm to about 700 nm. Here, the average particle size D of the inorganic particles is... 50 The particle size distribution can be obtained by randomly selecting about 20 particles from a scanning electron microscope image of inorganic particles, measuring their particle size (diameter, major axis, or major axis length), and then taking the size of the particles with a cumulative volume of 50% of the particle size distribution as the average particle size.
[0192] Organic and inorganic materials can be mixed in a single coating. In another embodiment, a coating comprising organic materials and a coating comprising inorganic materials can be stacked. The thickness of the coating can be from about 0.5 μm to about 20 μm, for example from about 1 μm to about 10 μm, or from about 1 μm to about 5 μm.
[0193] The rechargeable lithium battery according to the embodiments can be used in automobiles or various types of electronic devices such as mobile phones. However, this disclosure is not limited to these examples.
[0194] The following describes embodiments and comparative examples of the present invention. However, this disclosure is not limited to the following embodiments.
[0195] Example 1
[0196] (1) Preparation of positive electrode active material
[0197] (Preparation of core particles) By using particles with an average particle size of 17 μm D 50 Large lithium cobalt oxide (LCO, LiCoO2) particles with an average particle size of 5 μm D 50 Bimodal core particles were prepared by mixing lithium cobalt oxide (LCO, LiCoO2) particles in a weight ratio of 7:3.
[0198] (Preparation of graphite microparticles) Flake graphite (G5 (C-one), average particle size D) was prepared. 50 3 μm, in the Raman spectrum at 1350 cm⁻¹ -1 Nearby peak intensity (I) D ) at 1580 cm -1 Nearby peak intensity (I) G The ratio of (I) D / I G 0.12) was mixed with ZrO2 beads with a particle size of 2 mm, which were 10 times the weight of the flake graphite. The flake graphite was then milled with the beads at 1,000 rpm for 1 hour to prepare graphite microparticles. Here, the graphite microparticles had an average particle size D of 0.26 μm. 50And 0.28 in the Raman spectrum at 1350 cm⁻¹ -1 Nearby peak intensity (I) D ) at 1580 cm -1 Nearby peak intensity (I) G The ratio of (I) D / I G Additionally, 10 g of graphite microparticles were placed in a container, and pressure was applied for 1 minute at each pressure while varying the applied pressure. The powder conductivity was measured according to the applied pressure. The powder conductivity of the graphite microparticles was 4.4 S / cm at a pressure of 0.4 tons and 12.9 S / cm at a pressure of 2 tons.
[0199] (To obtain the positive electrode active material) 99.8 wt% of core particles and 0.2 wt% of graphite microparticles were placed in a dry mixer. The shear rate was adjusted to 7,000 s⁻¹. -1 After adjusting the rotation speed of the blades in the mixer to 4.7 m / s, the core particles and graphite microparticles were mixed for 10 minutes to prepare the positive electrode active material.
[0200] (2) Manufacturing of the positive electrode
[0201] A positive electrode active material slurry was prepared by dispersing 99.1 wt% of the positive electrode active material prepared in (1), 0.2 wt% of carbon nanotubes as a conductive material, and 0.7 wt% of polyvinylidene fluoride as a binder in N-methylpyrrolidone (NMP) as a solvent. The positive electrode active material slurry was coated onto a 12 μm thick aluminum substrate (current collector) and dried to form a positive electrode active material layer, which was then compressed to manufacture a positive electrode. In the manufactured positive electrode, the positive electrode active material layer had a concentration of 16 mg / cm³. 2 The loading level and density were 3.38 g / cc. Based on SEM analysis of the compressed positive electrode, the active material layer of the positive electrode had a thickness of approximately 50 μm.
[0202] (3) Manufacturing of rechargeable lithium battery cells
[0203] Prepare the positive electrode and lithium metal counter electrode manufactured in (2) above, and insert a separator (SH812J22HL (Senior)) with a polyethylene-polypropylene multilayer structure therebetween. Inject an electrolyte solution prepared by adding 1.3 M LiPF6 lithium salt to a solvent comprising ethylene carbonate, propylene carbonate and propyl propionate mixed in a volume ratio of 10:15:75 to manufacture a rechargeable lithium battery cell according to conventional methods.
[0204] Images of the sheet graphite and graphite particles used in the preparation of the positive electrode active material in Example 1 (1) were captured using a scanning electron microscope (SEM), and the images are shown in... Figure 5 and 6 middle. Specifically, Figure 5 These are scanning electron microscope images of the sheet graphite used in the preparation of the positive electrode active material in Example 1, and Figure 6 These are scanning electron microscope images of graphite particles obtained by crushing flake graphite.
[0205] Reference Figure 5 and Figure 6 It can be seen that graphite microparticles have a smaller average size D than flake graphite. 50 .
[0206] Example 2
[0207] The positive electrode active material, the positive electrode, and the rechargeable lithium battery cell were manufactured in the same manner as in Example 1, except that the shear rate was changed to 4,700 s in the preparation of the positive electrode active material in (1) of Example 1. -1 .
[0208] Example 3
[0209] The positive electrode active material, the positive electrode, and the rechargeable lithium battery cell were manufactured in the same manner as in Example 1, except that the shear rate was changed to 2,300 s in the preparation of the positive electrode active material in (1) of Example 1. -1 .
[0210] Example 4
[0211] (1) Preparation of positive electrode active material
[0212] Flake graphite (G5 (C-one), average particle size D) 50 3 μm, in the Raman spectrum at 1350 cm⁻¹ -1 Nearby peak intensity (I) D ) at 1580 cm -1 Nearby peak intensity (I) G The ratio of (I) D / I G ): 0.12) was mixed with ZrO2 beads with a particle size of 5 mm at 10 times the weight of the flake graphite, and the flake graphite was pulverized at 500 rpm for 30 minutes to prepare an average particle size D of 0.2 μm. 50 Graphite microparticles.
[0213] Separately from the preparation of graphite particles, TWCNTs (average length: 40 μm), used as raw materials for carbon nanotubes, were mixed with ZrO2 beads having a particle size of 5 mm. The carbon nanotube raw material was then pulverized at 500 rpm for 30 minutes to prepare carbon nanotubes with an average length of 10 μm. At this point, 10 g each of the carbon nanotube raw material and the carbon nanotubes were placed in a container and pressurized under varying pressure for 1 minute, and the powder conductivity was measured according to the applied pressure. The powder conductivity of the carbon nanotube raw material was 80.9 S / cm at a pressure of 0.4 tons and 203.0 S / cm at a pressure of 2 tons. Furthermore, the powder conductivity of the carbon nanotubes obtained by pulverizing the carbon nanotube raw material was 50.7 S / cm at a pressure of 0.4 tons and 80.7 S / cm at a pressure of 2 tons.
[0214] Based on a total of 100% by weight of the prepared graphite microparticles and carbon nanotubes, 17% by weight of the graphite microparticles and 83% by weight of the carbon nanotubes were mixed to prepare the coated raw materials.
[0215] In preparing particles with an average size of approximately 14 μm, D 50 And possessing LiNi 0.55 Co 0.15 Mn 0.30 After the O2 (NCM) composition is prepared into core particles (manufactured by XTC) in the form of secondary particles, 99.6% by weight of the core particles and 0.4% by weight of the coating material are placed in a mechanical fusion apparatus. The core particles and coating material are then fused at a temperature of 2,700 s. -1 After mixing at a shear rate of 4.7 m / s and a blade rotation speed of 4.7 m / s for 1 minute, the core particles and coating materials were then mixed at 5,400 s⁻¹. -1 The material was dry-mixed for 14 minutes at a shear rate of 9.4 m / s and a blade rotation speed of 9.4 m / s to prepare the positive electrode active material.
[0216] (2) Manufacturing of the positive electrode
[0217] A positive electrode active material slurry with a viscosity of 10,000 cps or lower was prepared by dispersing 96.1 wt% of the positive electrode active material prepared in (1) above, 1.82 wt% of carbon nanotubes and 0.78 wt% of carbon black as conductive materials, and 1.1 wt% of polyvinylidene fluoride and 0.2 wt% of polyacrylonitrile as binders in N-methylpyrrolidone (NMP) as a solvent. The positive electrode active material slurry was coated onto a 13.5 μm thick aluminum substrate (current collector) and dried to provide a positive electrode active material layer, which was then compressed to manufacture a positive electrode. In the positive electrode, the positive electrode active material layer had a viscosity of 6.0 mg / cm³. 2The loading level and density of 3.0 g / cc.
[0218] (3) Manufacturing of rechargeable lithium battery cells
[0219] Using the positive electrode and lithium metal counter electrode manufactured in (2) above, and inserting a separator (SH812J22HL (Senior), thickness: 16 μm) with a polyethylene-polypropylene multilayer structure between them, a rechargeable lithium battery cell was manufactured by injecting an electrolyte solution prepared by adding 1.15 M LiPF6 lithium salt to a solvent comprising ethylene carbonate, ethyl methyl carbonate and dimethyl carbonate mixed in a volume ratio of 20:40:40 into the obtained structure.
[0220] Images of the carbon nanotube raw materials and pulverized carbon nanotubes used in the preparation of the positive electrode active material in Example 4' (1) were captured using a scanning electron microscope (SEM), and the images are shown in... Figure 7 and 8 middle. Specifically, Figure 7 These are scanning electron microscope images of the surface of the carbon nanotube raw material used in the preparation of the positive electrode active material in Example 4, and Figure 8 These are scanning electron microscope images of the surface of carbon nanotubes obtained by crushing carbon nanotube raw materials.
[0221] Reference Figure 7 and 8 It can be seen that the pulverized carbon nanotubes have a smaller average length than the raw carbon nanotubes.
[0222] Example 5
[0223] (1) Preparation of positive electrode active material
[0224] Flake graphite (G5 (C-one), average particle size D) 50 3 μm, in the Raman spectrum at 1350 cm⁻¹ -1 Nearby peak intensity (I) D ) at 1580 cm -1 Nearby peak intensity (I) G The ratio of (I) D / I G 0.12) and TWCNTs (average length: 40 μm) as raw material for carbon nanotubes were mixed with ZrO2 beads with a particle size of 5 mm, which were 10 times the weight of the flake graphite. Subsequently, the flake graphite and carbon nanotube raw material were pulverized at 500 rpm for 30 minutes to prepare a mixture containing ZrO2 beads with an average particle size of 0.2 μm. 50A coating material consisting of graphite microparticles and carbon nanotubes with an average length of 10 μm was prepared. Based on a total of 100 wt% graphite microparticles and carbon nanotubes, 17 wt% graphite microparticles and 83 wt% carbon nanotubes were mixed to prepare the coating material. 10 g of the coating material was placed in a container and pressurized for 1 minute at varying pressures. The powder conductivity was then measured according to the applied pressure. The powder conductivity of the coating material was 94.4 S / cm at 0.4 tons and 458.8 S / cm at 2 tons.
[0225] In preparation of LiNi 0.55 Co 0.15 Mn 0.30 The composition of O2 is that of core particles in the form of secondary particles (average particle size D). 50 After forming core particles (approximately 14 μm in size) (manufactured by XTC), 99.6% by weight of the core particles and 0.4% by weight of the coating material were placed in a mechanical fusion apparatus. The core particles and coating material were then fused at a speed of 2,700 s. -1 After mixing at a shear rate of 4.7 m / s and a blade rotation speed of 4.7 m / s for 1 minute, the core particles and coating materials were then mixed at 5,400 s⁻¹. -1 The material was dry-mixed for 14 minutes at a shear rate of 9.4 m / s and a blade rotation speed of 9.4 m / s to prepare the positive electrode active material.
[0226] (2) Manufacturing of positive electrode and rechargeable lithium battery cell
[0227] The positive electrode and rechargeable lithium battery cell were manufactured in the same manner as in Example 4 using the positive electrode active material of Example 5 prepared in (1) above.
[0228] Images of the coated raw materials used in the preparation of the positive electrode active material in Example 5 (1) were captured using a scanning electron microscope (SEM), and the images are shown in... Figure 9 middle. Specifically, Figure 9 This is a scanning electron microscope image of the surface of the coated raw material used in the preparation of the positive electrode active material in Example 5, in which graphite microparticles and carbon nanotubes are combined.
[0229] Reference Figure 9 As can be seen, the crushing of flake graphite and the crushing of carbon nanotube raw materials are carried out together, thereby preparing a coating material in which graphite particles and carbon nanotubes are combined.
[0230] Comparative Example 1
[0231] The LiCoO2 (LCO) (bi-peak core particles) prepared for use in the preparation of the positive electrode active material in Example 1 (1) was used as the positive electrode active material. The prepared positive electrode active material was used to manufacture the positive electrode and the rechargeable lithium battery cell in the same manner as in Example 1.
[0232] Comparative Example 2
[0233] The positive electrode and rechargeable lithium battery cell were manufactured in the same manner as in Comparative Example 1, except that: in the preparation method of Comparative Example 1, 98.9% by weight of positive electrode active material (LCO) (bi-peak core particles), 0.2% by weight of conductive material and 0.9% by weight of binder were mixed.
[0234] Comparative Example 3
[0235] The positive electrode active material, positive electrode and rechargeable lithium battery cell were manufactured in the same manner as in Example 1, except that: in the preparation of the positive electrode active material in (1) of Example 1, carbon nanotubes (product name: Flotube6807, manufacturer: Cnano) were mixed with the core particles instead of graphite microparticles (amount of core particles: 99.8 wt%, amount of carbon nanotubes: 0.2 wt%).
[0236] Comparative Example 4
[0237] The positive electrode active material, positive electrode and rechargeable lithium battery cell were manufactured in the same manner as in Example 1, except that: in the preparation of the positive electrode active material in (1) of Example 1, Super P (manufacturer: TIMCAL) was mixed with the core particles (amount of core particles: 99.8 wt%, amount of Super P: 0.2 wt%) instead of graphite microparticles.
[0238] Comparative Example 5
[0239] The positive electrode active material, the positive electrode, and the rechargeable lithium battery cell were manufactured in the same manner as in Example 1, except that: in the preparation of the positive electrode active material in (1) of Example 1, reduced graphene was mixed with the core particles instead of graphite microparticles (amount of core particles: 99.8 wt%, amount of reduced graphene: 0.2 wt%).
[0240] Comparative Example 6
[0241] The LiNi used in the preparation of the positive electrode active material in Example 4 (1) 0.55 Co 0.15 Mn 0.30O2 was used as the positive electrode active material. The prepared positive electrode active material was used to manufacture the positive electrode and the rechargeable lithium battery cell in the same manner as in Example 4.
[0242] Comparative Example 7
[0243] (1) Preparation of positive electrode active material
[0244] In preparation of LiNi 0.55 Co 0.15 Mn 0.30 The composition of O2 is that of core particles in the form of secondary particles (average particle size D). 50 After the core particles (approximately 14 μm in diameter) were placed in a mechanical fusion apparatus, 99.6% by weight of the core particles and 0.4% by weight of TWCNTs (average length: 40 μm) as carbon nanotube raw materials were added. The core particles and carbon nanotube raw materials were then fused at 2,700 s⁻¹. -1 After mixing at a shear rate of 1 minute, the core particles and carbon nanotube raw materials were then subjected to a shear rate of 5,400 s⁻¹. -1 Dry mixing at a shear rate of 14 minutes was used to prepare the positive electrode active material.
[0245] (2) Manufacturing of positive electrode and rechargeable lithium battery cell
[0246] The positive electrode and rechargeable lithium battery cell were manufactured in the same manner as in Example 4 using the positive electrode active material of Comparative Example 7 prepared in (1).
[0247] Comparative Example 8
[0248] (1) Preparation of positive electrode active material
[0249] TWCNTs (average length: 40 μm), used as raw materials for carbon nanotubes, were mixed with ZrO2 beads with a particle size of 5 mm. Subsequently, the carbon nanotube raw materials were pulverized at 500 rpm for 30 minutes to prepare carbon nanotubes with an average length of 10 μm.
[0250] In preparation of LiNi 0.55 Co 0.15 Mn 0.30 The composition of O2 is that of core particles in the form of secondary particles (average particle size D). 50 After a depth of approximately 14 μm, 99.6% by weight of the core particles and 0.4% by weight of the carbon nanotubes were placed in a mechanical fusion apparatus. The core particles and carbon nanotubes were then fused at 2,700 s⁻¹. -1 After mixing at a shear rate of 1 minute, the core particles and carbon nanotubes were then subjected to a shear rate of 5,400 s⁻¹. -1 Dry mixing at a shear rate of 14 minutes was used to prepare the positive electrode active material.
[0251] (2) Manufacturing of positive electrode and rechargeable lithium battery cell
[0252] The positive electrode and rechargeable lithium battery cell were manufactured in the same manner as in Example 4 using the positive electrode active material of Comparative Example 8 prepared in (1).
[0253] Reference Example 1
[0254] The positive electrode and the rechargeable lithium battery cell were manufactured in the same manner as in Example 1, except that: in the manufacture of the positive electrode in (2) of Example 1, 98.7% by weight of positive electrode active material, 0.4% by weight of conductive material and 0.9% by weight of binder were mixed.
[0255] Evaluation 1: Scanning Electron Microscopy Image Analysis I
[0256] Images of the surface of the positive electrode active material particles of Example 1 and Comparative Examples 1 and 3 to 5 were captured using a scanning electron microscope, and the images are shown below. Figures 10 to 14 In addition, images of the cross-sections of the coating layers in the positive electrode active materials of Example 1 and Comparative Example 1 were taken using a transmission electron microscope, and the images are shown sequentially in the figures below. Figure 15 and 16 middle.
[0257] Reference Figures 10 to 16 As can be seen, unlike the positive electrode active material of Comparative Example 1, the positive electrode active material of Example 1 has a layered coating layer provided on the surface of the core particle. In addition, the coating layer of Example 1 is very thin, has a uniform thickness, and continuously wraps around the surface of the core particle.
[0258] On the other hand, it can be seen that Comparative Examples 3 to 5 were confirmed to have coatings provided on the surface of the core particles, but these coatings were not uniform and only partially covered the surface of the core particles. In other words, the coatings of Comparative Examples 3 to 5, derived from carbon nanotubes, Super P, and reduced graphene, were not uniform on the surface of the core particles.
[0259] Evaluation 2: Coating layer analysis of the positive electrode active material
[0260] The number and thickness of the coating layers of the positive electrode active materials in Examples 1 to 3, Comparative Examples 1 to 5, and Reference Example 1 were analyzed, and the results are shown in Table 1 below. The specific evaluation method is as follows.
[0261] The thickness and number of layers were measured by taking cross-sectional images of the positive electrode active material particles at 20 points using a scanning electron microscope and calculating the arithmetic mean of the measurement results.
[0262] Evaluation 3: Analysis of the physical properties of the positive electrode
[0263] The adhesion strength, resistivity, and density of the positive electrode active material layer to the current collector in Examples 1 to 3, Comparative Examples 1 to 5, and Reference Example 1 were analyzed, and the results are shown in Table 1. The specific evaluation methods are as follows.
[0264] (1) Adhesion strength of the positive electrode active material layer to the current collector
[0265] Twenty positive electrodes were prepared by cutting each electrode into 25 mm × 120 mm dimensions. After attaching double-sided adhesive tape to a glass substrate at room temperature, the positive electrode plates were attached to the tape and then rolled. Subsequently, after folding one end of the positive electrode plate 180°, one end of the positive electrode plate was pulled in the opposite direction at a speed of 0.5 mm / s to measure the force applied to it and thus obtain the adhesion strength of the positive electrode active material layer to the current collector. The adhesion strength was determined as the average value of the 20 samples.
[0266] (2) Resistivity of the positive electrode active material layer
[0267] The sheet resistance (thin-film resistance) of the positive electrode at contact was measured using an RM2610 (Hioki Corporation, Japan), and the resistance was measured again 10 seconds after contact. Resistivity (expressed by reflecting a thickness factor in the electrode plate resistance) was calculated by reflecting the weight and mixing density of the positive electrode mixture per unit area for each positive electrode. Specifically, the thickness of the active material layer of the positive electrode was directly measured using a micrometer, and the resistivity was calculated by the system by reflecting the measured thickness, the weight of the positive electrode mixture per unit area, and the mixing density for each electrode.
[0268] (3) Density of the positive electrode active material layer
[0269] In each positive electrode, the density of the active material layer is calculated by dividing the weight of the components other than the current collector by the volume.
[0270] Evaluation 4: Energy density analysis of rechargeable lithium battery cells
[0271] The rechargeable lithium-ion battery cells of Examples 1 to 3, Comparative Examples 1 to 5, and Reference Example 1 were subjected to energy density analysis, and the results are shown in Table 1. The specific evaluation method is as follows.
[0272] The rechargeable lithium-ion battery cells were initially charged at 25°C under constant current (0.35 C) and constant voltage (4.56 V, 0.05 C cutoff) conditions, and then discharged at a constant current (0.35 C) to 3.0 V for initial charge and discharge. The initial discharge capacity of the battery cells was measured.
[0273] In addition, the compressed electrode plate was stamped to a diameter of 14 mm to measure the thickness of the composite layer and calculate its density. Subsequently, the density of the composite layer was multiplied by the fraction of active material and the initial discharge capacity to calculate the energy density.
[0274] (Table 1)
[0275]
[0276]
[0277]
[0278] Referring to Table 1, it can be seen that in Examples 1 to 3, a coating layer containing graphene with a layered structure is provided on the surface of the core particle, wherein the coating layer has a thickness of several nanometers to tens of nanometers. Furthermore, as a result of analyzing the coating layers of the positive electrode active materials of Examples 1 to 3, it was found that in each of the positive electrode active materials, the interlayer spacing (d) of the graphene layered structure... 002 The value is 3.370 Å.
[0279] In the layered graphene-containing coatings of Examples 1 to 3, high electrode plate contact strength and low resistivity of the positive electrode active material layer are observed. Furthermore, in Examples 1 to 3, the amount of binder used in the manufacture of the positive electrode is reduced, while the amount of positive electrode active material is increased. As a result, the rechargeable lithium-ion battery cell exhibits high energy density characteristics. In particular, Example 1, in which binder and conductive material are included in smaller amounts than in Reference Example 1, exhibits excellent adhesion strength of the positive electrode active material layer to the current collector and high resistivity of the positive electrode active material layer, and also demonstrates very high energy density.
[0280] On the other hand, Comparative Examples 1 and 2, in which no coating layer is provided on the surface of the core particles, exhibited lower electrode plate contact forces or higher resistivity of the positive electrode active material layer than Examples 1 to 3. Furthermore, the energy density of the rechargeable lithium-ion battery cells of Comparative Examples 1 and 2 could not be measured because these comparative examples had significantly lower electrode plate contact forces and / or significantly higher resistivity of the positive electrode active material layer.
[0281] Furthermore, while the coating layer is provided on the surface of the core particles, Comparative Examples 3 and 4, derived from carbon nanotubes and Super P, contain amorphous carbon but do not have a layered structure with two or more layers. Therefore, compared to Examples 1 to 3, Comparative Examples 3 and 4 exhibit lower electrode plate contact force and higher resistivity of the positive electrode active material layer.
[0282] Furthermore, Comparative Example 5, in which the coating layer is provided on the surface of the core particle and is derived from reduced graphene, does not have a layered structure with two or more layers. Therefore, it is impossible to measure the energy density of the rechargeable lithium battery cell of Comparative Example 5 because it exhibits lower electrode plate contact force and higher resistivity of the positive electrode active material layer compared to Examples 1 to 3.
[0283] Evaluation 5: Electron Microscopy Image Analysis II
[0284] Images of the surface of the positive electrode active material particles of Examples 4 and 5 and Comparative Example 6 were captured using a scanning electron microscope, and the images are shown below. Figures 17 to 19 middle.
[0285] Reference Figures 17 to 19 As can be seen, unlike the positive electrode active material of Comparative Example 6, in the positive electrode active materials of Examples 4 and 5, a coating layer is provided on the surface of the core particle. Furthermore, the coating layer is thin and uniform, and continuously surrounds the surface of the core particle.
[0286] Furthermore, the cross-sections of the positive electrode active materials of Examples 4 and 5 were observed by transmission electron microscopy (TEM). The results confirmed that a coating layer comprising a layered graphene structure with two or more layers was formed on the surface of the respective core particles of the positive electrode active materials.
[0287] Evaluation 6: Performance Analysis of Rechargeable Lithium-ion Battery Cells
[0288] The rechargeable lithium-ion battery cells of Examples 4 and 5, as well as Comparative Examples 6 to 8, underwent performance analysis, and the results are shown in Table 2 below. The specific evaluation methods are as follows.
[0289] (1) Initial charge / discharge capacity and efficiency
[0290] The rechargeable lithium-ion battery cells were charged at 25°C under constant current (0.35 C) and constant voltage (4.56 V, 0.05 C cutoff) conditions, and then discharged to 3.0 V under constant current (0.35 C) conditions for initial charge and discharge. The initial charge capacity and initial discharge capacity were measured, and the ratio of the initial discharge capacity to the initial charge capacity was calculated as the initial efficiency.
[0291] (2) Ratio characteristics (output characteristics)
[0292] After the initial charging and discharging in (1), the battery cells were charged at 1.0 C in a voltage range of 3.0 V to 4.3 V at 25°C, and then discharged at 1.0 C or 30.0 C, and the capacity at each discharge rate was measured.
[0293] (3) Cycle life characteristics
[0294] After the initial charge and discharge in (1), the battery cells are charged and discharged at 3.0 C for 50 cycles or more at 25°C within a voltage range of 3.0 V to 4.3 V. At this point, the ratio of the discharge capacity of the 50th cycle to the initial discharge capacity is calculated.
[0295] (Table 2)
[0296]
[0297]
[0298] Referring to Table 2, it can be seen that Examples 4 and 5 exhibit high initial charge capacity, initial discharge capacity, and initial efficiency, and they also exhibit high rate capability and cycle life characteristics.
[0299] On the other hand, in the case of Comparative Example 6, since no coating layer was provided on the surface of the core particles, this comparative example exhibited lower initial efficiency, rate performance and cycle life characteristics compared to Examples 4 and 5.
[0300] Furthermore, because Comparative Examples 7 and 8 only include a carbon nanotube coating layer provided on the surface of the core particles, they exhibit lower initial efficiency, rate performance, and cycle life characteristics compared to Examples 4 and 5.
[0301] While this disclosure has been described with respect to embodiments that are now considered practical examples, it will be understood that this disclosure is not limited to the disclosed embodiments. This disclosure includes various modifications and equivalent arrangements.
[0302] <Explanation of reference numerals in the attached figures>
[0303] 100: Rechargeable lithium battery; 10: Positive electrode
[0304] 11: Positive electrode lead connector 12: Positive electrode terminal
[0305] 20: Negative electrode 21: Negative electrode lead connector
[0306] 22: Negative electrode terminal; 30: Diaphragm
[0307] 40: Electrode assembly; 50: Housing
[0308] 60: Sealing component; 70: Electrode terminal piece
[0309] 71: Positive electrode connector; 72: Negative electrode connector
Claims
1. Positive electrode active material, including: Including core particles of lithium transition metal complex compounds; and A coating layer disposed on the surface of the core particle, wherein each coating layer comprises graphene having a layered structure of 2 to 50 layers.
2. The positive electrode active material according to claim 1, wherein the coating layer comprises graphene having a layered structure of 7 to 40 layers.
3. The positive electrode active material according to claim 1, wherein the interlayer spacing d of the layered structure is... 002 The range is from 0.320 nm to 0.350 nm.
4. The positive electrode active material according to claim 1, wherein the thickness of the coating layer is 3 nm to 50 nm.
5. The positive electrode active material according to claim 1, wherein, The graphene in the coating layer is included in an amount from 0.02% to 3.0% by weight, based on a total of 100% by weight of the positive electrode active material.
6. The positive electrode active material according to claim 1, wherein the coating layer further comprises carbon nanotubes.
7. The positive electrode active material according to claim 1, wherein the graphene in the coating layer is derived from an average size D having an average size of less than or equal to 2.5 μm. 50 Graphite microparticles.
8. The positive electrode active material according to claim 1, wherein the graphene in the coating layer has a Raman spectrum of 0.15 to 0.50 at 1350 cm⁻¹. -1 Nearby peak intensity I D At 1580 cm -1 Nearby peak intensity I G The ratio I D / I G .
9. The positive electrode active material according to claim 1, wherein the core particles comprise a lithium cobalt-based oxide represented by chemical formula 1 or a lithium nickel-based oxide represented by chemical formula 2. Chemical formula 1 is: Li a1 Co x1 M 1 y1 O 2-b1 X b1 Where 0.9≤a1≤1.8, 0.7≤x1≤1, 0≤y1≤0.3, 0.9≤x1+y1≤1.1, and 0≤b1≤0.1, M 1 X is at least one of Al, B, Ba, Ca, Ce, Cr, Cu, Fe, Mg, Mn, Mo, Ni, Se, Si, Sn, Sr, Ti, V, W, Y, Zn, and Zr, and X is at least one of F, P, and S. Chemical formula 2 is: Li a2 Ni x2 M 2 y2 M 3 z2 O 2-b2 X b2 Where 0.9 ≤ a² ≤ 1.8, 0.3 ≤ x² ≤ 1, 0 ≤ y² ≤ 0.7, 0 ≤ z² ≤ 0.7, 0.9 ≤ x² + y² + z² ≤ 1.1, and 0 ≤ b² ≤ 0.1, M 2 and M 3 Each of the following is at least one of Al, B, Ba, Ca, Ce, Co, Cr, Cu, Fe, Mg, Mn, Mo, Nb, Si, Sn, Sr, Ti, V, Y, W, and Zr, and X is at least one of F, P, and S.
10. A method for preparing the positive electrode active material according to any one of claims 1 to 9, the method comprising: Prepare core particles comprising lithium transition metal complex compounds; Prepare materials with an average size D of less than or equal to 2.5 μm. 50 Graphite microparticles; as well as The core particles and the graphite microparticles are dry-mixed to obtain the positive electrode active material.
11. The method of claim 10, wherein the preparation of the graphite microparticles comprises having an average size D of 3 μm to 25 μm. 50 Flake graphite was pulverized to prepare a material with an average size D of less than or equal to 2.5 μm. 50 Graphite microparticles.
12. The method of claim 11, wherein ball milling is used to pulverize the flake graphite, and The ball milling process uses zirconia beads with a size of 1 mm to 25 mm and is carried out at a speed of 200 rpm to 5,000 rpm for 30 minutes to 4 hours.
13. The method of claim 10, wherein the graphite particles have a Raman spectral density of 0.15 to 0.50 at 1350 cm⁻¹. -1 Nearby peak intensity I D At 1580 cm -1 Nearby peak intensity I G The ratio I D / I G .
14. The method of claim 10, wherein, Based on the total amount of the core particles and the graphite microparticles (100% by weight), the graphite microparticles are mixed in an amount from 0.02% by weight to 3.0% by weight.
15. The method of claim 10, wherein the positive electrode active material is obtained by dry mixing the core particles and the graphite microparticles using a dry mixer at a speed of 1,000 s. -1 Up to 9,000s -1 The shear rate is mixed with the blade rotation speed of less than or equal to 20 m / s.
16. The method of claim 10, wherein, In obtaining the positive electrode active material, carbon nanotubes are further mixed with the core particles and the graphite microparticles.
17. The method of claim 16, further comprising preparing carbon nanotubes with an average length of 0.1 μm to 35 μm by pulverizing carbon nanotube raw materials having an average length greater than or equal to 40 μm. The preparation of the carbon nanotubes involves, during the step of preparing the graphite microparticles, combining carbon nanotube raw materials having an average length greater than or equal to 40 μm with an average size D of 3 μm to 25 μm. 50 The preparation of the carbon nanotubes can be carried out by co-pulverizing the flake graphite together with the graphite, or the preparation of the graphite nanoparticles can be carried out separately from the preparation of the graphite microparticles.
18. A rechargeable lithium battery, comprising: Positive electrode, comprising: Current collector, and The positive electrode active material layer on the current collector, The positive electrode active material layer comprises the positive electrode active material according to any one of claims 1 to 9; negative electrode; and Electrolytes.
19. The rechargeable lithium battery of claim 18, wherein the positive electrode active material layer further comprises a binder and a conductive material. in, The binder is included in an amount of 0.1% to 1.5% by weight, and the conductive material is included in an amount of 0% to 3% by weight, based on a total of 100% by weight of the positive electrode active material layer.
20. The rechargeable lithium battery according to claim 18, wherein the adhesion strength of the positive electrode active material layer to the current collector is greater than or equal to 0.5 gf / mm, and The resistivity of the positive electrode active material layer is less than or equal to 40 Ω·cm.